Manufacturing method of water-absorbent resin

By adding hydrogen peroxide to the production process of water-absorbing resin and drying at high temperature, the problems of the adhesion of the resin to the equipment and the load of the grinding equipment are solved, and the production efficiency and water absorption performance are improved.

JP7667806B2Active Publication Date: 2025-04-23NIPPON SHOKUBAI CO LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2022578536
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-29
Filing Date
2022-01-31
Publication Date
2025-04-23
Estimated Expiration
2042-01-31

Smart Images

  • Figure 0007667806000009
    Figure 0007667806000009
  • Figure 0007667806000001
    Figure 0007667806000001
  • Figure 0007667806000002
    Figure 0007667806000002
Patent Text Reader

Abstract

[Problem] To provide a method for producing a water-absorbent resin, wherein the method can efficiently yield a water-absorbent resin and the obtained water-absorbent resin has a high water absorbency under no pressure. [Solution] A water-absorbent resin production method comprises a polymerization step and a drying step. The polymerization step yields a hydrous crosslinked polymer gel by the polymerization of a monomer composition comprising an internal crosslinking agent and monomer. The drying step yields a dry polymer by drying the hydrous crosslinked polymer gel. The hydrous crosslinked polymer gel supplied to the drying step contains at least 50 ppm hydrogen peroxide with reference to the mass of the solids fraction of the hydrous crosslinked polymer gel. In addition, heating is carried out such that the maximum attained temperature of the hydrous crosslinked polymer gel in the drying step exceeds 160°C, and / or heating is carried out such that the maximum attained temperature of the dry polymer after the drying step exceeds 160°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a water-absorbent resin. [Background technology]

[0002] Super absorbent polymers (SAPs) are water-swellable, water-insoluble polymer gelling agents that are widely used in a variety of fields, including absorbent articles such as disposable diapers and sanitary napkins, agricultural and horticultural water retention agents, and industrial water-stopping agents.

[0003] The above-mentioned water-absorbent resins are made of many monomers and hydrophilic polymers as their raw materials. From the viewpoint of water-absorbing performance, the water-absorbent resins mainly composed of polymers constituted by acid group-containing unsaturated monomers are most widely produced industrially.

[0004] The water-absorbent resin is required to have various functions (higher physical properties) in accordance with the improvement of the performance of paper diapers, which are the main application of the water-absorbent resin. Specifically, in addition to the basic physical properties of water absorption capacity without load and water absorption capacity under load, various physical properties such as gel strength, water-soluble content, water content, water absorption rate, liquid permeability, particle size distribution, urine resistance, antibacterial properties, damage resistance, powder flowability, deodorizing properties, coloring resistance, low dust, and low residual monomers are required of the water-absorbent resin.

[0005] Water-absorbent resins are generally provided by polymerizing an acid group-containing unsaturated monomer, particularly by polymerizing an aqueous acrylic acid solution by aqueous solution polymerization or reversed-phase suspension polymerization to obtain a hydrogel polymer, which is then dried to a powder state. More specifically, a commercial method for producing water-absorbent resins typically includes a polymerization step, an optional gel crushing (granulation) step performed after or simultaneously with the polymerization, and a drying step of the granulated gel (Non-Patent Document 1).

[0006] In the industrial production of water-absorbent resins, which includes many of these processes, especially in continuous production, a problem in one process (e.g., temporary stoppage) leads to a decrease in the properties of the final product and a decrease in productivity. The hydrogel polymer is highly adhesive, so it easily adheres to the manufacturing equipment, causing damage to components and requiring a lot of time to clean the equipment during maintenance. In addition, when crushing the gel, the crusher is easily loaded.

[0007] In addition, in order to make paper diapers thinner, there is a tendency to reduce bulky pulp and increase the amount and role of water-absorbent resin used, and for this reason, importance is attached to the physical properties of the water-absorbent resin, in particular, its centrifugal retention capacity (CRC).

[0008] The adhesion of the hydrogel polymer to the production equipment and the increased load on the crushing device in the gel crushing as described above not only significantly reduce the productivity of the water-absorbent resin, but also cause a decrease in the physical properties of the water-absorbent resin. In general, the crosslink density of a water-absorbent resin with a high water-absorbency is low, so that the adhesion of the hydrogel polymer to the production equipment and the load are high. Therefore, such a problem is more prominent in a water-absorbent resin with a high water-absorbency. Furthermore, in the case of aqueous solution polymerization (e.g., belt polymerization) in which the production process includes a gel crushing process and no dispersion solvent is used in polymerization, the hydrogel directly contacts the production equipment (e.g., belt polymerization machine), the hydrogel transport equipment, storage equipment, gel crushing equipment, etc. of the water-absorbent resin, and therefore adhesion problems are likely to occur.

[0009] In order to solve such problems, methods such as Patent Documents 1 to 9 have been proposed as a method for reducing adhesion of the hydrous gel polymer to production equipment and the like and improving handleability to obtain a water-absorbent resin with a high water absorption capacity.

[0010] Specifically, Patent Document 1 proposes a method using a decomposable crosslinking agent to improve the handleability of the hydrogel and to increase the water absorption capacity. However, the decomposable crosslinking agent has a low crosslinking efficiency, so a large amount must be used, and the crosslinking agent is expensive. Furthermore, there is a problem that the decomposition product of the crosslinking agent remains in the water-absorbent resin. In addition, Patent Documents 2 to 4 propose a method of adding a specific surfactant or polyethylene glycol to the monomer, hydrogel, or device as a method for improving the handleability of the hydrogel polymer. However, these additives are expensive and have problems such as a decrease in the surface tension of the water-absorbent resin. Furthermore, Patent Document 5 proposes a method of suppressing adhesion of the hydrogel polymer by covering the contact surface between the hydrogel and the device with a resin film such as a fluororesin, but the adhesion prevention effect is insufficient, and the resin film is expensive and has poor durability. In addition, Patent Document 6 discloses a structure in which the belt base material is entirely made of resin and has a curved structure as a method for improving the release property of the hydrogel polymer. However, when using a resin substrate, it is necessary to use a thick substrate in order to obtain sufficient strength, and since the substrate is made of resin, heat transfer is poor, and heat removal is hardly expected. If polymerization is performed without sufficient heat removal, only a polymer with a small molecular weight is obtained, and there is a risk that sufficient performance will not be achieved. Patent documents 7 and 8 disclose a polymerization method for a water-absorbent resin in which the inner surface of a polymerization vessel is electropolished and the wall surface is cooled during polymerization in order to prevent adhesion of a hydrogel-like crosslinked polymer, but even if such a special treatment is performed, the effect is still insufficient and there is room for improvement. Patent document 9 discloses a polymerization method in which a hydrophobic organic solvent is added to the gas-liquid interface to prevent adhesion of hydrogel-like polymer particles to the inner wall of a polymerization vessel in reversed-phase suspension polymerization using a hydrophobic organic solvent.

[0011] Patent Document 10 discloses a method for producing a water-absorbent resin in which a hydroperoxide is added to a polymer polymerized (reverse-phase suspension polymerization) using a persulfate as a polymerization initiator, the water content is adjusted to 10 to 40% by weight, and crosslinking is performed with a crosslinking agent having two or more functional groups that can react with a carboxyl group. Patent Document 10 describes that such a production method can provide a water-absorbent resin with excellent salt resistance and water absorption rate. Patent Document 15 discloses a method for producing a water-absorbent resin in which hydrogen peroxide is added before surface crosslinking of water-absorbent resin particles.

[0012] Compared with reversed-phase suspension polymerization using a large amount of hydrophobic dispersed organic solvent and dispersant as described in Patent Documents 8 to 11, etc., and with gas-phase droplet polymerization as described in Patent Documents 12 and 15, etc., aqueous solution polymerization not using a dispersion medium such as an organic solvent or gas as disclosed in Patent Documents 1 to 7, 13, 14, etc. generally tends to cause a greater problem of adhesion of the hydrogel-like crosslinked polymer because the hydrogel-like polymer comes into direct contact with the apparatus. Patent Document 16 is another related technique. [Prior art documents] [Non-patent literature]

[0013] [Non-Patent Document 1] Modern Superabsorbent Polymer Technology(1998)p69-117 [Patent documents]

[0014] [Patent Document 1] International Publication No. 2006 / 062609 [Patent Document 2] Japanese Patent Application Publication No. 11-188726 [Patent Document 3] Japanese Patent Application Publication No. 57-34101 [Patent Document 4] JP 2001-342258 A [Patent Document 5] Japanese Patent Application Publication No. 60-055002 [Patent Document 6] Japanese Patent Application Publication No. 156102 / 1983 [Patent Document 7] Japanese Patent Application Publication No. 02-049002 [Patent Document 8] Japanese Patent Application Publication No. 03-041104 [Patent Document 9] Japanese Patent Application Publication No. 04-372603 [Patent Document 10] Japanese Unexamined Patent Publication No. 1205 / 1983 [Patent Document 11] International Publication No. 2003 / 059962 [Patent Document 12] International Publication No. 2008 / 009611 [Patent Document 13] Japanese Patent Application Publication No. 11-181005 [Patent Document 14] Japanese Patent Application Publication No. 03-174414 [Patent Document 15] International Publication No. 2020 / 089013 [Patent Document 16] China Patent Application Publication No. 101045789 Summary of the Invention [Problem to be solved by the invention]

[0015] Based on the problem that a water-absorbent resin having a high water-absorbency has high adhesion and load on a production apparatus due to high adhesion of a hydrous gel, the object of the present invention is to provide a production method for a water-absorbent resin, which has a high water-absorbency without load of the obtained water-absorbent resin and can efficiently produce the water-absorbent resin, in contrast to the above-mentioned Patent Documents 1 to 14 and Non-Patent Document 1, etc. [Means for solving the problem]

[0016] The method for producing a water-absorbent resin (first production method) of the present invention includes a polymerization step of polymerizing an aqueous monomer solution composition containing an internal crosslinking agent and a monomer to obtain a hydrogel-like crosslinked polymer, and a drying step of drying the hydrogel-like crosslinked polymer to obtain a dried polymer, wherein the hydrogel-like crosslinked polymer to be subjected to the drying step contains 50 ppm or more of hydrogen peroxide relative to the solid content mass of the hydrogel-like crosslinked polymer, and the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature reached by the polymer exceeds 160°C, and / or the dried polymer is heated after the drying step so that the maximum temperature reached by the polymer exceeds 160°C.

[0017] The method for producing a water-absorbent resin (second production method) of the present invention includes a polymerization step of polymerizing a monomer composition containing an internal crosslinking agent and a monomer to obtain a hydrogel-like crosslinked polymer, and a drying step of drying the hydrogel-like crosslinked polymer to obtain a dried polymer. In the polymerization step, a monomer composition having a monomer concentration of 30% by mass or more and containing 50 to 10,000 ppm of hydrogen peroxide relative to the solid mass of the monomer composition is polymerized, and the temperature of the monomer composition at the start of polymerization is 30° C. or more, the polymerization time from the start of polymerization until the polymerization temperature reaches the maximum temperature is within 30 minutes, and the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature of the hydrogel-like crosslinked polymer exceeds 160° C., and / or the dried polymer is heated after the drying step so that the maximum temperature of the dried polymer exceeds 160° C. The production method may optionally include a gel crushing step of crushing the hydrogel-like crosslinked polymer simultaneously with or after the polymerization step.

[0018] The method for producing a water-absorbent resin (third production method) of the present invention includes a polymerization step of polymerizing a monomer composition containing an internal crosslinking agent and a monomer to obtain a hydrogel-like crosslinked polymer, a gel crushing step of crushing the hydrogel-like crosslinked polymer simultaneously with or after the polymerization step, and a drying step of drying the hydrogel-like crosslinked polymer to obtain a dry polymer, in which 50 to 10,000 ppm of hydrogen peroxide is added to the solid content mass of the hydrogel-like crosslinked polymer in the gel crushing step, and the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature reached by the polymer exceeds 160°C, and / or the dried polymer is heated after the drying step so that the maximum temperature reached by the polymer exceeds 160°C. [Brief description of the drawings]

[0019] [Figure 1] 1 is a graph showing the results of an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention will be described in detail below, but the scope of the present invention is not limited to these descriptions, and in addition to the following examples, the present invention can be implemented by making appropriate modifications within the scope of the invention. Furthermore, the present invention is not limited to the following embodiments, and various modifications are possible within the scope of the claims. Other embodiments obtained by appropriately combining the technical means disclosed in each of the embodiments are also included in the technical scope of the present invention.

[0021] [1] Definitions of terms [1-1] “Water-absorbing resin” The "water-absorbent resin" in the present invention refers to a water-swellable, water-insoluble polymer gelling agent that satisfies the following physical properties: That is, the water-swellable polymer gelling agent has a CRC (centrifuge retention capacity) of 5 g / g or more as specified in NWSP 241.0.R2(15) (NWSP will be described later), and a water-insoluble polymer gelling agent has an Ext (water-soluble content) of 50 mass% or less as specified in NWSP 270.0.R2(15).

[0022] The water-absorbing resin can be designed according to its use and purpose, and is not particularly limited, but is preferably a hydrophilic cross-linked polymer obtained by (internal) cross-linking polymerization of an unsaturated monomer having an acid group (preferably a carboxyl group). In addition, the water-absorbing resin is not limited to a form in which the entire amount is a cross-linked polymer, and may be a composition containing additives, etc.

[0023] The "water absorbent resin" in the present invention may be surface cross-linked (also called post-cross-linked or secondary cross-linked) or may not be surface cross-linked. In the present invention, the water absorbent resin that has been subjected to a predetermined surface cross-linking treatment may be separately referred to as a surface cross-linked water absorbent resin.

[0024] [1-2] "Water absorbent" The "water absorbing agent" in the present invention means an absorbent gelling agent for aqueous liquids, containing a water absorbing resin as a main component. The water absorbing agent according to the present invention is suitably used as an absorbent article for absorbing aqueous liquids, and is particularly suitably used as an absorbent body for absorbent articles such as paper diapers (for infants and adults), sanitary napkins, and incontinence pads. The water absorbing agent of the present invention preferably contains a water absorbing resin in an amount of 60 to 100 mass%, 70 to 100 mass%, 80 to 100 mass%, or 90 to 100 mass%, and may contain various additives described later as other components. That is, a water absorbing resin composition in which these components are integrated also falls within the category of the water absorbing agent.

[0025] [1-3] Definition of evaluation method "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015", which was jointly issued by EDANA (European Disposables And Nonwovens Association) and INDA (Association of the Nonwoven Fabrics Industry) to standardize evaluation methods for nonwoven fabrics and their products in the United States and Europe, and indicates standard measurement methods for water-absorbent resins. Unless otherwise specified, in the present invention, the physical properties of the water-absorbent resin are measured in accordance with "Non-Woven Standard Procedures-Edition 2015". Evaluation methods not described in NWSP are measured by the methods and conditions described in the examples.

[0026] [1-4] Other In this specification, the term "X to Y" indicating a range means "X or more and Y or less." In addition, unless otherwise noted, the unit of mass "t (ton)" means "metric ton," and "ppm" means "ppm by mass" or "ppm by weight." Furthermore, "mass" and "weight," "parts by mass" and "parts by weight," "% by mass" and "% by weight" are treated as synonyms, respectively. In addition, "acid (salt)" means "acid and / or its salt," and "(meth)acrylic" means "acrylic and / or methacrylic," respectively.

[0027] [2] Manufacturing method of water-absorbent resin The production method according to the present invention is a method for producing a water-absorbent resin, comprising: a polymerization step of polymerizing a monomer composition containing an internal crosslinking agent and a monomer to obtain a hydrogel-like crosslinked polymer; and a drying step of drying the hydrogel-like crosslinked polymer to obtain a dried polymer, wherein the hydrogel-like crosslinked polymer subjected to the drying step contains 50 ppm or more of hydrogen peroxide relative to the solid content mass of the hydrogel-like crosslinked polymer, and the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature it reaches exceeds 160°C, and / or the dried polymer is heated after the drying step so that the maximum temperature it reaches exceeds 160°C.

[0028] Alternatively, the production method according to the present invention is a method for producing a water-absorbent resin, comprising a polymerization step of polymerizing a monomer composition containing an internal crosslinking agent and a monomer to obtain a hydrogel-like crosslinked polymer, and a drying step of drying the hydrogel-like crosslinked polymer to obtain a dried polymer, wherein in the polymerization step, a monomer composition having a monomer concentration of 30% by mass or more and containing 50 to 10,000 ppm of hydrogen peroxide relative to the solid content mass of the monomer composition is polymerized, in which the temperature of the monomer composition at the start of polymerization is 30° C. or more, the polymerization time from the start of polymerization until the polymerization temperature reaches the maximum temperature is within 30 minutes, and the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature reaches more than 160° C., and / or the dried polymer is heated after the drying step so that the maximum temperature reaches more than 160° C. The production method may optionally include a gel crushing step of crushing the hydrogel-like crosslinked polymer simultaneously with or after the polymerization step.

[0029] Alternatively, the production method according to the present invention is a method for producing a water-absorbent resin, comprising: a polymerization step of polymerizing a monomer composition containing an internal crosslinking agent and a monomer to obtain a hydrogel-like crosslinked polymer; a gel crushing step of crushing the hydrogel-like crosslinked polymer simultaneously with or after the polymerization step; and a drying step of drying the hydrogel-like crosslinked polymer to obtain a dry polymer, wherein in the gel crushing step, 50 to 10,000 ppm of hydrogen peroxide is added relative to the solid content mass of the hydrogel-like crosslinked polymer, and the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature reached by the crosslinked polymer exceeds 160°C, and / or the dried polymer is heated after the drying step so that the maximum temperature reached by the dry polymer exceeds 160°C.

[0030] According to such a production method, adhesion of the hydrous gel to the production equipment is small, and when the hydrous gel is crushed, the load on the crushing equipment is small, so that the handling property in the production process of the water absorbent resin is improved, and the production efficiency is improved. In addition, the water absorption capacity without load of the obtained water absorbent resin is high.

[0031] In this manufacturing method, the polymer is crosslinked by an internal crosslinking agent. By having such a crosslinked structure, the gel structure of the hydrogel becomes stronger, and the adhesion of the hydrogel decreases. Therefore, adhesion to a polymerization device or the like is reduced, and when the hydrogel is crushed, the load on the crushing device is reduced. On the other hand, when the crosslink density in the polymer increases due to internal crosslinking, the water absorption performance of the water-absorbent resin, particularly the water absorption capacity under no pressure, tends to decrease. This is considered to be because the swelling of the water-absorbent resin is suppressed by increasing the crosslink density. In this manufacturing method, the hydrogel-like crosslinked polymer before drying contains hydrogen peroxide at a specific concentration (ppm). Then, the hydrogel-like crosslinked polymer containing hydrogen peroxide is heated to a temperature exceeding 160°C, whereby the water absorption capacity can be efficiently improved.

[0032] Therefore, according to the present production method, in the production process, by making the crosslinked structure inside the polymer dense, it is possible to facilitate the handling and workability during production and improve the production efficiency, and further, by making the crosslinked structure sparse to some extent after the drying step, it is possible to improve the water absorption properties, particularly the water absorption capacity without load, of the obtained water absorbent resin.

[0033] It should be noted that the above assumption does not limit the technical scope of the present invention in any way.

[0034] This production method includes, for example, (1) a step of preparing a monomer composition containing an internal crosslinking agent and a monomer, (2) a polymerization step of polymerizing the monomer composition to obtain a hydrogel-like crosslinked polymer, (4) a drying step, and, as necessary, (3) a gel crushing step and (5) a surface crosslinking step. The gel crushing step is a step in which the hydrogel-like crosslinked polymer obtained in the polymerization step is crushed simultaneously with and / or after polymerization to obtain a particulate hydrogel-like crosslinked polymer (hereinafter also referred to as a "particulate hydrogel").

[0035] Hydrogen peroxide is added in any one of the production steps before drying of the hydrogel crosslinked polymer.

[0036] Specifically, hydrogen peroxide is preferably added in any one or more of the following production steps (1) to (4).

[0037] (1) preparing a monomer composition containing an internal crosslinking agent and a monomer (Mode 1); (2) A polymerization step of polymerizing a monomer composition to obtain a hydrogel-like crosslinked polymer (form 2); (3) Gel crushing step (form 3), (4) Fine powder granulation process (Form 4).

[0038] Furthermore, it is more preferable that hydrogen peroxide is added in any one or more of the above production steps (1) to (3).

[0039] The method of adding hydrogen peroxide is not particularly limited, but it is preferable to add hydrogen peroxide in the form of an aqueous solution in which hydrogen peroxide is dissolved, since it is easy to add hydrogen peroxide. The concentration of hydrogen peroxide in the aqueous solution is not particularly limited, but is usually about 1 to 40% by mass. As the water used in the hydrogen peroxide aqueous solution, for example, deionized water (ion-exchanged water), pure water, ultrapure water, distilled water, etc. can be used. In addition, the hydrogen peroxide aqueous solution may contain a small amount of a hydrophilic solvent. As the hydrophilic solvent, alcohols such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and t-butyl alcohol can be exemplified. The solvent used in combination is used at, for example, 0 to 10% by mass relative to water. The temperature when hydrogen peroxide or the hydrogen peroxide aqueous solution is added is not particularly limited as long as the solution to be added can maintain its fluidity, and may be, for example, in the range of -10 to 100°C, more preferably 0 to 30°C.

[0040] After the drying step, the hydrogel crosslinked polymer and / or the dried polymer is heated to a maximum temperature exceeding 160°C.

[0041] Specifically, in the following steps, the hydrogel crosslinked polymer and / or the dried polymer is preferably heated so that the maximum temperature reached exceeds 160°C.

[0042] (A) a drying step of drying the hydrogel crosslinked polymer to obtain a dry polymer (form A); (B) Surface cross-linking heat treatment process (form B).

[0043] Each step will be described in detail below.

[0044] [2-1] Step of preparing monomer composition This step is a step of preparing a monomer composition (hereinafter, also simply referred to as a composition) containing a monomer constituting a polymer and an internal crosslinking agent. The monomer composition is usually an aqueous solution containing a monomer and an internal crosslinking agent. Note that, a monomer slurry (a dispersion exceeding the saturated concentration of the monomer) can also be used within a range in which the water absorption performance of the obtained water absorbent resin is not reduced, but for the sake of convenience, such a slurry is also included in the monomer composition in this section.

[0045] The monomer used preferably contains an acid group-containing unsaturated monomer as a main component. Here, the above-mentioned "main component" means that the amount (content) of the acid group-containing unsaturated monomer used is usually 50 mol% or more, preferably 70 mol% or more, more preferably 90 mol% or more (upper limit 100 mol%) based on the total monomers (excluding the internal crosslinking agent) used in the polymerization reaction of the water absorbent resin.

[0046] The acid group in the acid group-containing unsaturated monomer is not particularly limited, but examples thereof include a carboxyl group, a sulfone group, and a phosphoric acid group. Examples of the acid group-containing unsaturated monomer include (meth)acrylic acid, (anhydrous) maleic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloyloxyethanesulfonic acid, 2-(meth)acryloyloxypropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate. From the viewpoint of water absorption performance, preferred are (meth)acrylic acid, (anhydrous) maleic acid, itaconic acid, and cinnamic acid, more preferred are (meth)acrylic acid, and most preferred is acrylic acid.

[0047] It is preferable that a part or all of the acid groups contained in the acid group-containing unsaturated monomer contained in the composition are neutralized. The salt of the acid group-containing unsaturated monomer is appropriately selected from salts with inorganic cations such as alkali metal salts, alkaline earth metal salts, and ammonium salts, and salts with basic substances such as amine-based organic compounds having amino groups or imino groups. Among them, a salt with a monovalent cation is more preferable, and at least one selected from alkali metal salts, ammonium salts, and amine salts is more preferable, and an alkali metal salt is even more preferable. Among the alkali metal salts, at least one selected from sodium salts, lithium salts, and potassium salts is even more preferable, and sodium salts are particularly preferable. The neutralization of the acid groups contained in the acid group-containing unsaturated monomer is not limited to the case where it is carried out in this step, and may be carried out at any stage of the production process. From the viewpoint of uniformly neutralizing the acid group-containing unsaturated monomer, it is preferable that the neutralization of the acid groups contained in the acid group-containing unsaturated monomer is carried out before the step of drying the particulate hydrogel-like crosslinked polymer. In other words, neutralization of the acid group contained in the acid group-containing unsaturated monomer is preferably carried out in the step of preparing the monomer composition, or in the gel crushing step simultaneously with and / or after polymerization, more preferably in the step of preparing the monomer composition.

[0048] The above acid group-containing unsaturated monomer Or a hydrogel cross-linked polymer The neutralizing agent used for neutralizing the above-mentioned acid group-containing insoluble monomer is not particularly limited, but may be any of the following: compound Any inorganic substance such as sodium hydroxide, potassium hydroxide, sodium carbonate, or ammonium carbonate may be used. Basic Compounds A basic substance such as an amine-based organic compound having an amino group or an imino group is appropriately selected and used. Two or more basic substances may be used in combination as the neutralizing agent.

[0049] In order to solve the problems of the present invention, the number of moles of the neutralization salt relative to the total number of moles of the acid group-containing unsaturated monomer and its neutralization salt (hereinafter referred to as "neutralization rate") is preferably 40 mol% or more, more preferably 45 mol% or more, and even more preferably 50 mol% or more. From the viewpoint of water absorption performance, the neutralization rate is preferably 80 mol% or less, 78 mol% or less, and 75 mol% or less, in that order. The neutralization rate is adjusted to, for example, 40 mol% to 80 mol%, 45 mol% to 78 mol%, and 50 mol% to 75 mol%. The suitable range of the neutralization rate is also the same in the case of post-neutralization (neutralization in a hydrous gel polymer). If the neutralization rate is low, the adhesion of the hydrous gel crosslinked polymer obtained after polymerization increases, and adhesion to the device may increase.

[0050] The neutralization rate may be adjusted before the start of the polymerization reaction of the acid group-containing unsaturated monomer, during the polymerization reaction of the acid group-containing unsaturated monomer, or on the hydrogel-like crosslinked polymer obtained after the polymerization reaction of the acid group-containing unsaturated monomer (post-neutralization). The neutralization rate may be adjusted at one of the stages before the start of the polymerization reaction, during the polymerization reaction, or after the polymerization reaction, or at multiple stages. The neutralizing agent may be added once or in multiple stages (for example, two-stage neutralization). Two-stage neutralization involves adding the neutralizing agent in two stages.

[0051] In a preferred embodiment, when an internal crosslinking agent and a monomer are polymerized to obtain a hydrogel crosslinked polymer, the monomer contains an acid group-containing unsaturated monomer as a main component, and the number of moles of the neutralized salt relative to the total number of moles of the acid group-containing unsaturated monomer and its neutralized salt (neutralization rate) is 50 mol% or more. By neutralizing to a certain extent before polymerization in this way, a uniformly neutralized hydrogel polymer can be obtained, and when a surface treatment step is performed, uniform surface crosslinking is achieved.

[0052] The composition may contain monomers other than the acid group-containing unsaturated monomer.

[0053] The monomer other than the acid group-containing unsaturated monomer may be any compound that can be polymerized to become a water-absorbing resin. For example, amide group-containing unsaturated monomers such as (meth)acrylamide, N-ethyl (meth)acrylamide, and N,N-dimethyl (meth)acrylamide; amino group-containing unsaturated monomers such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylamide; mercapto group-containing unsaturated monomers; phenolic hydroxyl group-containing unsaturated monomers; lactam group-containing unsaturated monomers such as N-vinylpyrrolidone; etc.

[0054] In order to solve the problems of the present invention, the monomer concentration in the composition (=total monomer amount / composition amount, where the monomer includes monomers other than the acid group-containing unsaturated monomer) is preferably 10% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, even more preferably 30% by mass to 70% by mass, and particularly preferably 40% by mass to 60% by mass, from the viewpoint of the physical properties and productivity of the water-absorbent resin. By having the monomer concentration in the composition within the above range, adhesion to a production device, etc. of the hydrogel-like crosslinked polymer after polymerization can be further reduced.

[0055] The composition contains an internal crosslinking agent. Use of the internal crosslinking agent can reduce the tackiness of the resulting hydrogel-like crosslinked polymer, and can suppress adhesion to and excessive load on production equipment, etc.

[0056] The internal crosslinking agent may have a total of two or more unsaturated bonds or reactive functional groups in one molecule. For example, examples of internal crosslinking agents having a plurality of polymerizable unsaturated groups (copolymerizable with monomers) in the molecule include N,N-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin (meth)acrylate, glycerin acrylate methacrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, pentaerythritol hexa(meth)acrylate, triallyl cyanurate, triallyl isocyanurate, triallyl phosphate, trimethylolpropane di(meth)allyl ether, poly(meth)allyl ether of polyol having 2 to 10 carbon atoms, pentaerythritol triallyl ether, and tetraallyloxyethane. Examples of internal crosslinking agents having multiple reactive functional groups (which can react with functional groups of monomers (e.g., carboxy groups)) in the molecule include triallylamine, polyallyloxyalkane, (poly)ethylene glycol diglycidyl ether, glycerol diglycidyl ether, ethylene glycol, polyethylene glycol, propylene glycol, glycerin, 1,4-butanediol, pentaerythritol, ethylenediamine, ethylene carbonate, propylene carbonate, and polyethyleneimine (note that here, cyclic carbonates such as ethylene carbonate are crosslinking agents that further generate functional groups OH by reacting with carboxyl groups). Examples of internal crosslinking agents having polymerizable unsaturated groups and reactive functional groups in the molecule include glycidyl (meth)acrylate. Two or more of these may be used in combination.

[0057] Among these internal crosslinking agents, from the viewpoint of the effects of the present invention, preferably, a compound having a plurality of polymerizable unsaturated groups in the molecule, more preferably, a compound having a (poly)alkylene oxide structure in the molecule, even more preferably, a compound having a polyethylene glycol structure, even more preferably, an acrylate compound having a polyethylene glycol structure, particularly preferably, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, and most preferably, polyethylene glycol diacrylate. In the hydrogel obtained by using these internal crosslinking agents, the effect that the water absorption capacity (particularly the water absorption capacity without pressure) is easily improved by heating in the drying process or the subsequent process is obtained.

[0058] In solving the problems of the present invention, the amount of the internal crosslinking agent used is appropriately set according to the type of monomer and the internal crosslinking agent. From the viewpoint of increasing the gel strength of the obtained water-absorbent resin and preventing adhesion of the hydrogel to a polymerization apparatus or the like, the amount of the internal crosslinking agent used in the polymerization step is preferably 0.005 mol% or more, more preferably 0.01 mol% or more, and even more preferably 0.02 mol% or more, based on the total amount of the monomers used. In addition, from the viewpoint of improving the water absorption performance of the water-absorbent resin, it is preferably 5 mol% or less, more preferably 2 mol% or less, and may be 1 mol% or less, 0.5 mol% or less, less than 0.1 mol%, or 0.05 mol% or less. If the amount of the internal crosslinking agent used is too small, the adhesion of the hydrogel-like crosslinked polymer after polymerization increases, and if the amount of the internal crosslinking agent used is too large, the water absorption capacity of the obtained water-absorbent resin may be reduced.

[0059] The water used in the monomer composition may be, for example, deionized water (ion-exchanged water), pure water, ultrapure water, distilled water, or the like, with deionized water (ion-exchanged water) being preferred.

[0060] The monomer composition may contain a small amount of a hydrophilic solvent. Examples of the hydrophilic solvent include alcohols such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and t-butyl alcohol. The hydrophilic solvent used in combination is used in an amount of, for example, 0 to 10% by mass relative to water.

[0061] Other substances Within the scope of achieving the object of the present invention, the following substances (hereinafter referred to as "other substances") may be added to the monomer composition.

[0062] Specific examples of other substances include polymerization inhibitors, chain transfer agents such as thiols, thiolic acids, secondary alcohols, amines, and hypophosphites, foaming agents such as carbonates, bicarbonates, azo compounds, and bubbles, chelating agents such as ethylenediaminetetra(methylenephosphinic acid) and metal salts thereof, ethylenediaminetetraacetic acid and metal salts thereof, and diethylenetriaminepentaacetic acid and metal salts thereof, hydrophilic polymers such as polyacrylic acid (salts) and crosslinked products thereof (for example, fine powders made of water-absorbent resins), starch, cellulose, starch-cellulose derivatives, and polyvinyl alcohol, etc. The other substances may be used alone or in combination of two or more.

[0063] The amount of other substances used is not particularly limited, but the total concentration of the other substances is preferably 10% by mass or less, more preferably 0.001% by mass to 5% by mass, and particularly preferably 0.01% by mass to 1% by mass, relative to the total amount of monomers.

[0064] The present invention is characterized in that the hydrogel crosslinked polymer to be subjected to the drying step contains 50 ppm or more of hydrogen peroxide relative to the solid content, and is heated at a temperature exceeding 160° C. (preferably 170 to 220° C.) during and / or after the drying step. Here, the method for obtaining a hydrogel crosslinked polymer containing 50 ppm or more of hydrogen peroxide relative to the solid content may be either (1) a method of preparation before the polymerization step or (2) a method of preparation after the polymerization step and before the drying step, or a combination of (1) and (2).

[0065] Specific examples of methods for adjusting the content of hydrogen peroxide in the hydrous gel polymer include the following (1) and (2).

[0066] Method for adjusting hydrogen peroxide content up to the polymerization process (1); In this method, a predetermined amount of hydrogen peroxide is added in the monomer composition preparation step or polymerization step, and polymerization conditions are selected such that 50 ppm or more of hydrogen peroxide remains after polymerization (e.g., polymerization time, polymerization temperature, adjustment of the amount of hydrogen peroxide decomposition promoter such as ultraviolet light or a reducing agent, co-use of a hydrogen peroxide stabilizer, etc.). In other words, the method of adding hydrogen peroxide can be selected from adding it in the monomer composition preparation step (form 1) and adding it in the polymerization step (form 2). In this case, the preferred polymerization conditions are not particularly limited as long as 50 ppm or more of hydrogen peroxide remains in the hydrogel-like crosslinked polymer after polymerization, but the second production method described below (a method of performing high-temperature initiation, high-concentration, short-time polymerization in the presence of 50 ppm or more of hydrogen peroxide) are preferably used.

[0067] (2) A method for adjusting the hydrogen peroxide content after the polymerization process and before the drying process; Hydrogen peroxide is added to the hydrogel crosslinked polymer after the polymerization step to adjust the hydrogen peroxide content to 50 ppm or more (including hydrogen peroxide optionally used in the polymerization step). Specifically, hydrogen peroxide may be added after the polymerization step and before the drying step. The timing of adding hydrogen peroxide includes a conveying step in which the hydrogel polymer discharged from the polymerization apparatus after polymerization is conveyed to the subsequent step, a (optionally provided) storage step, a (optionally provided) aging step, a gel crushing step, and adding hydrogen peroxide to the hydrogel crosslinked polymer so that the hydrogen peroxide content is 50 ppm or more between these steps. Among these, addition in the gel crushing step (form 3) is preferred. This adjustment method can be selected as the third manufacturing method described later (a method in which 50 ppm or more of hydrogen peroxide is added in the gel crushing step after the polymerization step).

[0068] (Form 1) In the first embodiment, hydrogen peroxide is added in the preparation process of a monomer composition containing an internal crosslinking agent and a monomer. That is, a monomer composition containing hydrogen peroxide and a monomer is obtained, and the monomer is polymerized in the next step using the composition.

[0069] The order of addition of the monomer, the internal crosslinking agent, and the hydrogen peroxide is not particularly limited, and may be any of the following: adding hydrogen peroxide to an aqueous solution containing the monomer and the internal crosslinking agent; adding the monomer, the internal crosslinking agent, and the hydrogen peroxide to water at the same time; adding the monomer and the internal crosslinking agent to an aqueous hydrogen peroxide solution.

[0070] In the embodiment 1, when hydrogen peroxide is contained in the monomer composition, the amount of hydrogen peroxide added is preferably 50 ppm or more relative to the monomer composition (solid content), although it depends on the polymerization conditions (polymerization time, polymerization temperature, etc.), considering the improvement of the physical properties of the obtained water absorbent resin, particularly the water absorption capacity without pressure. That is, in one of the preferred embodiments of the present invention, a monomer composition containing 50 ppm or more of hydrogen peroxide relative to the solid content is polymerized in the next polymerization step to obtain a hydrogel crosslinked polymer. Here, the solid content refers to the total mass of the monomers in the monomer composition. The polymerization conditions are appropriately selected so as to obtain a desired hydrogen peroxide concentration as described above, and the amount of hydrogen peroxide remaining in the hydrogel polymer after polymerization (ppm) may be measured. When hydrogen peroxide is contained in the composition in Form 1, the amount of hydrogen peroxide added is preferably 50 ppm (0.005% by mass) to 10,000 ppm (1.0% by mass), more preferably 100 ppm (0.01% by mass) to 5,000 ppm (0.5% by mass) relative to the monomer composition (solid content (total mass of monomers)). Form 1 may be combined with, for example, any one or more of Forms 2 to 4 other than Form 1, in which case the amount of hydrogen peroxide added is appropriately adjusted so that the amount of hydrogen peroxide is 50 ppm or more relative to the solid content mass of the hydrogel crosslinked polymer.

[0071] [2-2] Polymerization process This step is a step of polymerizing the monomer composition to obtain a hydrogel-like crosslinked polymer (hereinafter, sometimes referred to as "hydrogel").

[0072] The polymerization reaction can be carried out by decomposing the polymerization initiator added to the monomer composition and generating a reaction initiation terminal. The polymerization initiator may be added in advance to a composition containing a monomer and an internal crosslinking agent. The polymerization initiator is not particularly limited because it is appropriately selected depending on the polymerization form, etc., but examples thereof include a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a combination of these, or a redox-based polymerization initiator combined with a reducing agent that promotes the decomposition of the polymerization initiator. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 are used. Among them, in the high-temperature initiated polymerization, which is a preferred embodiment, a thermally decomposable polymerization initiator is preferred from the viewpoint of polymerization efficiency. In addition, from the viewpoint of the handleability of the polymerization initiator and the physical properties of the water-absorbing resin, preferably a peroxide or an azo compound, more preferably a peroxide, and even more preferably a persulfate such as sodium persulfate, ammonium persulfate, or potassium persulfate is used. Hydrogen peroxide is known as a polymerization initiator, particularly as an oxidizing agent for a redox-based polymerization initiator. In consideration of the polymerization efficiency, however, as the polymerization initiator in the present embodiment, it is preferable to use another thermally decomposable polymerization initiator in combination with hydrogen peroxide, and it is particularly preferable to use hydrogen peroxide in combination with a persulfate.

[0073] In this embodiment, hydrogen peroxide can be used as an oxidizing agent for the redox polymerization initiator, and can be used in combination with a reducing compound such as L-ascorbic acid or sodium hydrogen sulfite. In the present invention, as described above, a suitable form is one in which a sufficient amount of hydrogen peroxide remains in the hydrogel crosslinked polymer after the polymerization step in the drying step, and the hydrogel crosslinked polymer to be dried may contain 50 ppm or more of hydrogen peroxide relative to its solid mass. That is, when a redox polymerization initiator using a reducing agent and an oxidizing agent in combination is used, it is preferable to add an excess amount of hydrogen peroxide relative to the amount of the reducing compound added so that a sufficient amount of hydrogen peroxide remains in the hydrogel crosslinked polymer after the polymerization step in the drying step. The amount of hydrogen peroxide added (ppm) is preferably 10 times or more by mole relative to the reducing compound, more preferably 100 times or more by mole, and even more preferably 1000 times or more by mole. More preferably, the polymerization is performed without using a reducing compound such as L-ascorbic acid or sodium hydrogen sulfite, which is also a decomposing agent for hydrogen peroxide. The amount of the reducing compound added is preferably 10 ppm or less, more preferably 1 ppm or less, even more preferably 0.1 ppm or less, and most preferably substantially 0 ppm (absent), based on the solid content of the hydrogel crosslinked polymer. In the present embodiment, a particularly preferred embodiment is one in which the reducing compound is in the above range (particularly absent), and the polymerization initiator consists of only hydrogen peroxide and persulfate.

[0074] The amount of the thermally decomposable polymerization initiator or photodecomposable polymerization initiator other than hydrogen peroxide used is preferably 0.001 mol % to 1 mol %, more preferably 0.001 mol % to 0.5 mol %, even more preferably 0.005 to 0.5 mol %, and still more preferably 0.01 to 0.5 mol %, based on the total amount of monomers.

[0075] In addition to the above-mentioned method of carrying out a polymerization reaction by decomposition of a polymerization initiator, there is a method of irradiating with active energy rays such as radiation, electron beams, ultraviolet rays, etc. Furthermore, irradiation with active energy rays may be used in combination with addition of a polymerization initiator.

[0076] The polymerization form is not particularly limited. From the viewpoint of water absorption performance and ease of polymerization control, etc., preferably, droplet polymerization in a gas phase, aqueous solution polymerization, reversed-phase suspension polymerization (droplet polymerization in a hydrophobic organic solvent is also included as an example of reversed-phase suspension), more preferably, aqueous solution polymerization, reversed-phase suspension polymerization, and even more preferably, aqueous solution polymerization are mentioned. For details on reversed-phase suspension polymerization,

[0016] to

[0033] of Japanese Patent No. 4969778, specifically, Example 1 can be referred to. Among them, continuous aqueous solution polymerization is particularly preferable, and examples thereof include continuous belt polymerization and continuous kneader polymerization, and more preferably, continuous belt polymerization. By adopting continuous aqueous solution polymerization, the production efficiency of the water absorbent resin is improved. The polymerization may be carried out in a batch manner. The polymerization may also be a stationary polymerization method.

[0077] In addition, in order to solve the problems of the present invention, preferred forms of aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization". "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of the monomer composition of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point), and "high-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration in the monomer composition of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination. By adopting these polymerization methods ("high-temperature initiated polymerization" and "high-concentration polymerization"), adhesion to the production equipment of the hydrogel-like crosslinked polymer can be further reduced, and the added hydrogen peroxide can be allowed to remain in the hydrogel-like crosslinked polymer at 50 ppm or more.

[0078] To bring the monomer composition to a desired temperature (e.g., 40°C or higher), the polymerization vessel itself may be heated, or the monomer composition may be heated in line when being supplied to the polymerization vessel. Preferably, neutralization is performed during preparation of the monomer composition, and the heat of neutralization of the monomer is used to raise the temperature of the monomer composition. Note that the generation of heat of neutralization and / or heat of hydration is preferred because it can be effectively utilized not only to raise the temperature of the monomer composition, but also to remove dissolved oxygen.

[0079] In order to effectively utilize the heat of neutralization and / or heat of hydration, it is preferable to carry out the neutralization in an adiabatic state, and it is more preferable to carry out the polymerization continuously while carrying out the neutralization continuously. Therefore, for example, it is preferable to use a container that minimizes heat radiation, and the material used is preferably a resin, rubber, or stainless steel with the non-contact parts covered with a heat-insulating material.

[0080] In order to solve the problems of the present invention, the polymerization time may be appropriately determined depending on the type of monomer and polymerization initiator, the polymerization temperature, etc., but from the viewpoint of the amount of hydrogen peroxide remaining after polymerization, the polymerization time (from the start of polymerization to the time when the polymerization temperature reaches the maximum temperature) is preferably short (short-time polymerization is preferable), specifically, preferably within 30 minutes, more preferably within 20 minutes, even more preferably within 10 minutes, even more preferably within 5 minutes, and particularly preferably within 2 minutes. In addition, in the reversed-phase suspension polymerization as in Patent Documents 8 to 11, the heating time for polymerization is generally long, at 1 hour or more, so there is a problem from the viewpoint of the amount of hydrogen peroxide remaining after polymerization, or it is difficult to perform heating at 160°C or more in the drying process after polymerization, etc., because a large amount of hydrophobic organic solvent is used. Even the long-time aqueous solution polymerization described in Patent Document 14 has a problem from the viewpoint of the amount of hydrogen peroxide remaining after polymerization, so in order to solve the problems of the present invention, the short-time polymerization and further the high-temperature initiation polymerization are preferable. The use of hydrogen peroxide as a polymerization initiator is also known in Patent Documents 8 and 14, but Patent Document 8 (long-term reversed-phase suspension polymerization) and Patent Document 14 (long-term redox polymerization) do not suggest the amount of hydrogen peroxide remaining after polymerization or the problems and effects of the present application. Note that, as a means for carrying out polymerization in a short time, although not limited thereto, for example, the above-mentioned high-temperature initiated polymerization can be mentioned.

[0081] Therefore, in a preferred embodiment, in the polymerization step, the monomer concentration of the monomer composition is 30% by mass or more, the temperature of the monomer composition at the start of polymerization is 30° C. or more, and the polymerization time from the start of polymerization until the polymerization temperature reaches the maximum temperature is within 30 minutes. The start of polymerization refers to the time when the temperature of the monomer composition is increased. The lower limit of the polymerization time is not particularly limited as long as the polymerization proceeds sufficiently, but is preferably 5 seconds or more, more preferably 10 seconds or more, and even more preferably 15 seconds or more. Another preferred embodiment is that in the polymerization step, a monomer composition having a monomer concentration of 30% by mass or more and containing 50 to 10,000 ppm of hydrogen peroxide relative to the solid content mass of the monomer composition is polymerized, in which the temperature of the monomer composition at the start of polymerization is 30° C. or more, and the polymerization time from the start of polymerization until the polymerization temperature reaches the maximum temperature is within 30 minutes.

[0082] In order to solve the problems of the present invention, the solid content of the hydrogel (hereinafter, gel solid content) is preferably 25% by mass or more, more preferably 25% by mass to 75% by mass, even more preferably 25% by mass to 65% by mass, even more preferably 25% by mass to less than 60% by mass, and particularly preferably 40% by mass to less than 60% by mass. There is no particular limit to the means for achieving these concentrations, but for example, the above-mentioned "high-temperature initiated polymerization" and / or "high-concentration polymerization" are preferably used. The gel solid content (mass%) is measured by the method described in the examples below. If the gel solid content (mass%) is low, the gel may become more sticky. If the gel solid content is excessively high, physical properties such as water absorption capacity (g / g) may decrease, or gel crushing may become difficult if necessary. If the gel solid content is high, the effect of hydrogen peroxide may not be easily manifested.

[0083] (Form 2) In form 2, hydrogen peroxide is added in the polymerization step (particularly, to the monomer composition in the polymerization machine). Here, the timing of adding hydrogen peroxide is not particularly limited, but specifically, hydrogen peroxide is added just before polymerization of the monomer composition (specifically, for example, adding hydrogen peroxide simultaneously with a polymerization initiator); hydrogen peroxide is added during polymerization of the monomer (specifically, for example, adding hydrogen peroxide in a gel crushing step during the polymerization step when polymerization and gel crushing are performed simultaneously as in continuous kneader polymerization); hydrogen peroxide is added to a hydrogel obtained by polymerizing the monomer composition; and the like. As described above, the above form 2 can be taken in the adjustment method (1) up to the polymerization step.

[0084] Hydrogen peroxide may be added in the polymerization step to the monomer before polymerization (polymerization rate 0%), or to a mixture of the hydrogel and monomer after the start of polymerization (polymerization rate over 0%), or these may be used in combination. Note that although a technique using 50 ppm or more of hydrogen peroxide in polymerization (e.g., Patent Document 1) is known, the amount of hydrogen peroxide remaining after polymerization varies greatly depending on the polymerization conditions (polymerization time, polymerization temperature, etc.), and Patent Document 1 does not suggest heating to 160°C or higher after polymerization, so the use of 50 ppm or more of hydrogen peroxide during polymerization (e.g., Patent Document 1) does not suggest the present invention at all.

[0085] The amount of hydrogen peroxide added to the hydrogel is appropriately set in consideration of the polymerization conditions selected and the amount of hydrogen peroxide (ppm) remaining before drying. For example, in consideration of the improvement of the physical properties of the obtained water-absorbent resin, particularly the water absorption capacity under no pressure (g / g), the amount is preferably 50 ppm (0.005 mass%) or more, more preferably 50 ppm (0.005 mass%) to 10000 ppm (1.0 mass%), and even more preferably 100 ppm (0.01 mass%) to 5000 ppm (0.5 mass%) relative to the solid mass of the hydrogel-like crosslinked polymer. In addition, the amount of hydrogen peroxide added when hydrogen peroxide is added immediately before or during polymerization of the monomer composition can be the amount of hydrogen peroxide described in the above-mentioned (form 1). In addition, form 2 may be combined with any one or more of forms 1, 3, and 4 other than form 2, in which case the amount of hydrogen peroxide added is appropriately adjusted so that the amount of hydrogen peroxide is 50 ppm or more relative to the solid mass of the hydrogel-like crosslinked polymer.

[0086] As in (Form 1), the polymerization method applied in (Form 2) is appropriately selected from the above methods, but it is preferable to select polymerization conditions such that the amount of hydrogen peroxide in the hydrogel before the drying step is 50 ppm or more, including hydrogen peroxide added after polymerization as necessary. As specific polymerization methods, one or more of the above-mentioned "high-temperature initiation polymerization", "high-concentration polymerization" and "short-time polymerization", and particularly two or three of them (the above-mentioned "high-temperature initiation polymerization", "short-time polymerization" and "high-concentration polymerization") are preferably applied in the present invention.

[0087] (Method for producing second water-absorbent resin) That is, as a suitable means for achieving the embodiments 1 and 2, the present invention preferably applies a method in which a monomer composition containing 50 to 10,000 ppm (more preferably 100 to 5,000 ppm) of hydrogen peroxide is polymerized under the above-mentioned conditions of "high-temperature initiation polymerization", "short-time polymerization", and "high-concentration polymerization", and heating at a temperature exceeding 160°C during and / or after the drying step.

[0088] That is, in the present invention, as a second production method, there is provided a production method for a water-absorbent resin, comprising a polymerization step of polymerizing a monomer composition containing an internal crosslinking agent and a monomer to obtain a hydrogel-like crosslinked polymer, and a drying step of drying the hydrogel-like crosslinked polymer to obtain a dry polymer, in which in the polymerization step, a monomer composition having a monomer concentration of 30 mass% or more and containing 50 to 10,000 ppm of hydrogen peroxide relative to the solid content mass of the monomer composition is polymerized, in which the temperature of the monomer composition at the start of polymerization is 30°C or more, the polymerization time from the start of polymerization until the polymerization temperature reaches the maximum temperature is within 30 minutes (preferably within 20 minutes), and the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature reaches exceeds 160°C, and / or the dried polymer is heated after the drying step so that the maximum temperature reaches exceeds 160°C. The production method may optionally include a gel crushing step of crushing the hydrogel crosslinked polymer simultaneously with or after the polymerization step.

[0089] [2-3] Gel crushing process This step is an optional step of crushing the hydrogel crosslinked polymer obtained in the polymerization step simultaneously with and / or after polymerization to obtain a particulate hydrogel crosslinked polymer. This step may be performed two or more times to obtain a particulate hydrogel of a predetermined particle size. In addition, when a particulate hydrogel of a desired particle size is obtained in the polymerization step, such as in reverse phase suspension polymerization or gas phase polymerization, this step may not be performed. In addition, if necessary, a shredding step may be performed using a roller cutter, a guillotine cutter, or the like to cut or roughly crush the hydrogel crosslinked polymer into a size that can be put into a gel crushing device after the polymerization step and before the gel crushing step. In particular, when the polymerization step is belt polymerization and a sheet-like or block-like hydrogel is obtained, it is preferable to perform the shredding step. The size of the hydrogel to be subjected to the gel crushing step (preferably obtained through the shredding step) is not particularly limited, but is preferably 10 mm or more, more preferably 3 cm or more. The upper limit is not particularly limited, but may be 3 m or less, or may be 2 m or less.

[0090] The hydrogel to be subjected to the drying step in the next step is preferably one that has been subjected to this step. This is because heating is efficiently performed in the drying step, and the effect of adding hydrogen peroxide is further enhanced. That is, the present production method includes a gel crushing step of crushing the hydrogel crosslinked polymer obtained in the polymerization step, and the hydrogel crosslinked polymer to be dried is preferably a particulate hydrogel crosslinked polymer crushed in the gel crushing step. In addition, in the gel crushing step, a form in which hydrogen peroxide is added to the hydrogel crosslinked polymer and / or the particulate hydrogel crosslinked polymer is also preferred. According to this form, hydrogen peroxide can be efficiently added to the hydrogel before drying. When crushing the gel, in consideration of the physical properties of the obtained water-absorbent resin, particularly the improvement of the water absorption capacity without pressure, the amount of hydrogen peroxide added is preferably 50 ppm or more relative to the solid mass of the hydrogel crosslinked polymer.

[0091] When only a part of the acid group-containing unsaturated monomer is neutralized in the composition preparation step (2-1) or polymerization is carried out without neutralization in the polymerization step (2-2), neutralization can be carried out in this gel crushing step.

[0092] In the production method of the present invention, the type of gel crushing device is not particularly limited as long as a particulate hydrogel of a predetermined particle size can be obtained without impairing the water absorption performance. For example, a gel crushing device equipped with multiple rotating stirring blades such as a batch or continuous double-arm kneader, a single-screw extruder, a twin-screw extruder, a meat chopper, etc. can be mentioned.

[0093] In the gel crushing step, the polymer gel may be mixed with the above-mentioned additives or post-neutralization of the acid groups in the crosslinked polymer may be performed. The final neutralization rate is within the above-mentioned range, and sodium hydroxide, (hydrogen)carbonate, or an aqueous solution or dispersion thereof is used for post-neutralization after polymerization.

[0094] A surface cross-linking agent described below may be added before and / or during the gel crushing step. In this case, surface cross-linking is carried out simultaneously with drying in a drying device.

[0095] A gel fluidizer may be added before and / or during the gel crushing step. The addition of the gel fluidizer suppresses adhesion between hydrogel particles in the drying step described below, and improves the water absorption rate of the resulting water absorbent resin. Even in an embodiment that does not require a gel crushing step, the above effect can be obtained by adding a gel fluidizer to the particulate hydrogel before the drying step. Specifically, it is preferable to add the gel fluidizer during preparation of the monomer composition and / or during the gel crushing step. The amount of the gel fluidizer to be added is preferably 0 to 1% by weight or less, more preferably 0.001 to 0.5% by weight, based on the solid content of the monomer or hydrogel crosslinked polymer.

[0096] Examples of the gel fluidizing agent include anionic, cationic, nonionic and amphoteric surfactants, low molecular weight and high molecular weight surfactants thereof, and polymer lubricants. As the gel fluidizing agent of the present invention, a surfactant is preferred.

[0097] (Surfactant) Specific examples of surfactants used in gel fluidizing agents include: (1) sucrose fatty acid esters, polyglycerin fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerin fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkylaryl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl gluconamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, phosphate esters of polyoxyethylene alkyl ethers, and phosphate esters of polyoxyethylene alkyl allyl ethers. Nonionic surfactants such as esters, (2) alkyl dimethyl amino acetic acid betaines such as capryl dimethyl amino acetic acid betaine, lauryl dimethyl amino acetic acid betaine, myristyl dimethyl amino acetic acid betaine, and stearyl dimethyl amino acetic acid betaine, alkyl amidopropyl betaines such as lauric acid amidopropyl betaine, coconut oil fatty acid amidopropyl betaine, and palm kernel oil fatty acid amidopropyl betaine, alkyl hydroxysulfobetaines such as lauryl hydroxysulfobetaine, and alkyl carboxymethyl hydroxyethyl imidazolinium betaine such as 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, (3) anionic surfactants such as alkyl amino diacetate monoalkali metals such as lauryl amino diacetate monosodium, lauryl amino diacetate potassium, and myristyl amino diacetate sodium, and (4) cationic surfactants such as long-chain alkyl dimethyl amino ethyl quaternary salts. Two or more of these may be used in combination.

[0098] (polymer lubricant) Specific examples of polymer lubricants used in gel fluidizers include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified ethylene-propylene-diene terpolymer (EPDM), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, polyalkylene oxide such as ethyl cellulose, ethylhydroxyethyl cellulose, polyethylene glycol, and polysiloxane modified with side chain and / or terminal polyether. The molecular weight (weight average molecular weight) of these is preferably selected appropriately within the range of 2 to 2,000,000, more preferably 4 to 1,000,000. Two or more of these may be used in combination.

[0099] Furthermore, as the gel fluidizing agent, these polymeric lubricants may be used in combination with the above-mentioned surfactants.

[0100] The type and amount of the gel fluidizing agent are appropriately adjusted in consideration of the fluidity of the particulate hydrogel in the gel crushing step and the drying step. In addition, as form 3, when hydrogen peroxide is added to the hydrogel in this step, it may be added by mixing with the gel fluidizing agent or may be added separately to the hydrogel. As described above, the hydrogel may be crushed simultaneously with the polymerization, in which case forms 2 and 3 are carried out in parallel.

[0101] (Form 3) In form 3, hydrogen peroxide is added after the polymerization step (after the end of the polymerization step) and before the drying step. Considering the effect of the present invention of reducing the load on the crushing device, hydrogen peroxide is preferably added during or before the gel crushing step. The addition of hydrogen peroxide in the gel crushing step is not limited to the form of adding a hydrogel polymer and hydrogen peroxide to a gel crushing device, and the addition of hydrogen peroxide in the gel crushing step in the present invention also includes a form in which hydrogen peroxide is added before the hydrogel polymer after the polymerization step to be crushed is introduced into the gel crushing device, and hydrogen peroxide is mixed into the hydrogel at the same time as the gel is crushed. Hydrogen peroxide may be added in a shredding step in which the hydrogel is cut or roughly crushed to a size that can be introduced into the gel crushing device before the gel crushing step. When hydrogen peroxide is added in the gel crushing step, it is preferable to add hydrogen peroxide before and / or during the gel crushing step and mix it thoroughly when the gel is crushed. The size of the hydrous gel when hydrogen peroxide is added during the shredding step / before the gel crushing step / gel crushing step is not particularly limited, but is preferably 1 mm or more, more preferably 5 mm or more, and even more preferably 3 cm or more. It is preferable that the gel size when hydrogen peroxide is mixed is a certain size or more, because the effect of adding hydrogen peroxide is more easily exhibited. The upper limit of the hydrous gel size when hydrogen peroxide is added during the shredding step / before the gel crushing step / gel crushing step is not particularly limited, but may be 3 m or less, or may be 2 m or less. The amount of hydrogen peroxide added to the hydrous gel polymer is appropriately set in consideration of the amount of hydrogen peroxide remaining before drying, and is, for example, preferably 50 ppm (0.005 mass%) or more, more preferably 50 ppm (0.005 mass%) to 10000 ppm (1.0 mass%), and even more preferably 100 ppm (0.01 mass%) to 5000 ppm (0.5 mass%) relative to the solid content mass of the hydrous gel crosslinked polymer. The above-mentioned (Mode 3) addition method can be selected as the method (2) for adjusting the amount of hydrogen peroxide in the hydrogel crosslinked polymer after the polymerization step. In addition, Mode 3 may be combined with at least one of Modes 1, 2, and 4 other than Mode 3, in which case the amount of hydrogen peroxide added is appropriately adjusted to 50 ppm or more of hydrogen peroxide based on the solid content mass of the hydrogel crosslinked polymer.A preferred embodiment of the present invention further includes a gel-crushing step of crushing the hydrogel-like crosslinked polymer simultaneously with or after the polymerization step, and in the gel-crushing step, 50 to 10,000 ppm of hydrogen peroxide is added relative to the solid content mass of the hydrogel-like crosslinked polymer.

[0102] The amount of hydrogen peroxide remaining after the addition is not determined simply by the amount added, but is affected by the temperature and polymerization rate of the hydrogel-like crosslinked polymer, as well as the time until the drying step, and therefore, if necessary, these conditions can be controlled by measuring the amount of hydrogen peroxide (ppm) in the hydrogel-like crosslinked polymer before drying.

[0103] The polymerization rate of the particulate hydrogel in solving the problems of the present invention is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more, from the viewpoint of suppressing aggregation during drying of the particulate hydrogel-like crosslinked polymer and reducing the residual monomer in the obtained water-absorbent resin. If a drying step is carried out using a hydrogel having a low polymerization rate containing a large amount of unreacted monomer, hydrogen peroxide may be consumed before the drying step, or a polymerization reaction may proceed during drying, resulting in regeneration or by-production of large-sized gel particles from small-sized gel particles. Due to the large-sized gel particles, problems such as a decrease in the water absorption rate of the obtained water-absorbent resin, large particles of the dried product, and generation of fine powder due to re-crushing to the target product particle size occur. In order to avoid this problem, it is preferable to set the polymerization rate of the hydrogel within the above range.

[0104] The upper limit of the polymerization rate of the (particulate) hydrogel is not particularly limited, and 100% by mass is ideal, but a long polymerization time and strict polymerization conditions are required for a high polymerization rate, which may lead to a decrease in productivity and physical properties, so the upper limit is 99.95% by mass, further 99.9% by mass, and usually about 99.8% by mass. Typically, it is 98 to 99.99% by mass.

[0105] The polymerization rate of the hydrogel can be measured as follows. After sampling the hydrogel, 1.00 g of the hydrogel is immediately put into 1000 g of ion-exchanged water at room temperature (the polymerization reaction essentially stops at this point), and the mixture is stirred at 300 rpm for 2 hours, followed by filtration to remove insoluble matter. The amount of monomer extracted in the filtrate obtained by the above operation is measured using a liquid chromatograph. When the amount of the monomer is taken as the residual monomer amount m (g), the polymerization rate C (mass%) of the hydrogel is calculated according to the following (formula 1), and the residual monomer rate R (mass%) of the hydrogel is calculated according to the following (formula 2). It is preferable to measure the polymerization rate immediately after sampling the hydrogel, but if it takes time from sampling to measurement, it is necessary to perform a polymerization termination operation by forced cooling (contact with dry ice, liquid nitrogen, ice water, etc.).

[0106] C (mass%)=100×{1-m / (α×M / 100)} (Formula 1) R (mass%)=100-C (Formula 2) In the formula 1, M is the mass (g) of the hydrogel, α is the solid content (mass%) of the hydrogel, and in the formula 2, C is the polymerization rate (mass%) of the hydrogel.

[0107] In order to solve the problems of the present invention, the CRC (centrifuge retention capacity) of the (particulate) hydrogel is preferably 80 g / g or less, more preferably 50 g / g or less, even more preferably 45 g / g or less, and particularly preferably 40 g / g or less, in terms of solid content. The lower limit is preferably 5 g / g or more, more preferably 10 g / g or more, even more preferably 15 g / g or more, and particularly preferably 20 g / g or more. A suitable range is 5 g / g to 80 g / g, more preferably 10 g / g to 50 g / g, even more preferably 15 g / g to 45 g / g, and particularly preferably 20 g / g to 40 g / g. In terms of suppressing adhesion to the device, a preferred embodiment may be that the CRC (centrifuge retention capacity) of the (particulate) hydrogel is 43 g / g or less, 40 g / g or less, or 38 g / g or less. The solid content conversion means that the physical properties such as CRC are measured using a hydrogel, and then converted into the physical properties per solid content of the water-absorbent resin in the hydrogel (for example, for a hydrogel with a water content of 50% (solid content of 50%), the physical properties are converted into the measured physical properties of the hydrogel x 2). Specifically, the properties are measured by the method described in the examples below.

[0108] In order to solve the problems of the present invention, the solid content of the (particulate) hydrogel (hereinafter, gel solid content) is preferably 25% by mass or more. From the viewpoints of suppressing aggregation of hydrogel particles after gel crushing, energy required for crushing, drying efficiency, and absorption performance, the gel solid content is more preferably 25% by mass to 75% by mass, even more preferably 25% by mass to 65% by mass, even more preferably 25% by mass or more and less than 60% by mass, and particularly preferably 40% by mass or more and less than 60% by mass. In addition, if the gel solid content is high, the effect of hydrogen peroxide may not be easily exhibited. The gel solid content is measured by the method described in the examples below.

[0109] In order to solve the problems of the present invention, the preferred particle size of the (particulate) hydrogel is a mass average particle size of the particulate hydrogel crosslinked polymer in terms of solid content within the range of 5000 μm or less, with 3000 μm or less and 1000 μm or less being more preferred in that order. In this embodiment, the adhesion of the hydrogel to the device is reduced, so the load on the device is small and the particle size of the particulate hydrogel can be made small. The lower limit of the particle size of the (particulate) hydrogel is, for example, 50 μm or more in terms of the mass average particle size in terms of solid content. The mass average particle size in terms of solid content can be measured by the method described in the following examples. In addition, in the gel crushing step, as a method of controlling within the above range, U.S. Patent Nos. 6,906,159, 5,275,773, 6,100,305, 6,140,395, 6,875,511, U.S. Patent Application Publication Nos. 2004 / 234,607, 2005 / 46069, etc. are adopted. In addition, the load on the device during gel crushing can be evaluated by GGE(1) and GGE(2) described in International Publication No. 2011 / 126079 (U.S. Patent Application Publication No. 2013 / 026412) and the magnitude of the current value (A) during operation of the gel crushing device.

[0110] In this production method (first production method), the content of hydrogen peroxide in the hydrogel crosslinked polymer to be dried is 50 ppm or more relative to the hydrogel solid mass. When the hydrogen peroxide content is 50 ppm or more, the water absorption capacity without load (CRC) of the obtained water absorbent resin is significantly improved. As an example of a means for adjusting the content of hydrogen peroxide, hydrogen peroxide is added in the specific high-temperature initiation, high-concentration, short-time polymerization (second production method) or added in the gel crushing step (third production method). The hydrogen peroxide added in an amount of 50 ppm or more in the second or third method remains mostly (70% or more) in the hydrogel crosslinked polymer to be dried, so that it is preferably applied to the method of adding 50 ppm or more relative to the hydrogel solid mass (first production method).

[0111] When controlling the amount of hydrogen peroxide in the second and third production methods, the shorter the time from the end of the polymerization step to the drying step and / or the time from the gel crushing step to the drying step, the better in controlling the amount of hydrogen peroxide in the hydrogel crosslinked polymer, and it is preferably within 1 hour, further 30 minutes or less, more preferably 20 minutes or less, 10 minutes or less, and 5 minutes or less, in that order, and the temperature of the hydrogel crosslinked polymer during this period is preferably controlled to 100° C. or less, further 90 to 30° C., or 80 to 40° C. The time from the end of the polymerization step to the drying step and / or the time from the gel crushing step to the drying step is usually 30 seconds or more.

[0112] In the first to third manufacturing methods, the content (or amount used) of hydrogen peroxide in the hydrogel subjected to drying is preferably more than 100 ppm, more preferably 150 ppm, and even more preferably 200 ppm or more, from the viewpoint of improving the water absorption capacity without pressure. Moreover, the content (solid content equivalent) of hydrogen peroxide in the hydrogel subjected to drying is preferably 50,000 ppm or less, more preferably 10,000 ppm or less, even more preferably 5000 ppm or less, and even more preferably 3000 ppm or less, from the viewpoint of suppressing an excessive increase in soluble matter.

[0113] [2-4] Drying process This step is a step of drying the (particulate) hydrogel obtained in the polymerization step and / or gel crushing step to a desired resin solid content to obtain a dried polymer. The resin solid content is determined from the loss on drying (the change in mass when 1 g of the water-absorbent resin is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85 to 99% by mass, even more preferably more than 90% by mass and 99% by mass or less, even more preferably more than 90% by mass and 98% by mass or less, and particularly preferably 92 to 97% by mass.

[0114] The method for drying the particulate hydrogel is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high-temperature water vapor, etc. Among these, hot air drying is preferred from the viewpoint of drying efficiency.

[0115] The set temperature of the dryer used for drying is, in order of preference, more than 160°C, more than 160°C and 250°C or less, 170-220°C, 170-200°C, 180-200°C, and more than 180°C and 200°C or less. By controlling the set temperature in this manner, the maximum temperature of the hydrogel crosslinked polymer during the drying process can be easily set to a desired temperature, and deterioration of the water-absorbent resin is suppressed. That is, in a preferred embodiment of the present invention, the hydrogel crosslinked polymer is dried in a dryer set to a temperature exceeding 160°C.

[0116] The hot air drying method includes a method of drying in a stationary state, a method of drying in an agitated state, a method of drying in a vibrated state, a method of drying in a fluidized state, a method of drying with an air flow, and the like. Among these, from the viewpoint of efficiency, agitation drying or stationary drying is preferred, agitation drying using a rotating device or ventilation band drying is more preferred, and hot air drying using continuous ventilation band drying (continuous ventilation band drying) is particularly preferred. When hot air drying is performed, the hot air temperature is, in order of preference, more than 160°C, more than 160°C and 250°C or less, 170 to 220°C, 170 to 200°C, 180 to 200°C, and more than 180°C and 200°C or less. By controlling the hot air temperature in this way, it is easy to set the maximum temperature of the hydrogel crosslinked polymer during the drying process to a desired temperature, and deterioration of the water-absorbent resin is suppressed.

[0117] As another suitable form, agitation drying using an agitation drying device is adopted. This agitation drying is a type of drying operation by heat transfer, and can be applied to the material to be dried, preferably continuously, using an indirect heating method. Therefore, it has the advantage of high drying efficiency. The agitation method and form of the agitation drying device are not particularly limited, and it is sufficient that the contents in the drying device are agitated by agitation means such as an arm, blade, paddle, or other agitation blade or a rotating cylinder. In other words, the above-mentioned agitation drying device includes a container rotation type dryer in which the container itself that contains the contents rotates, vibrates, and swings; a mechanical agitation type dryer that agitates the contents with a rotating shaft equipped with an agitation blade such as an arm, blade, or paddle; a floating agitation type dryer that suspends the contents with a gas such as air; a flow path division type dryer that divides the flow path by gravity and a branch plate, etc.; a high-speed shear type dryer; an impact type dryer, etc. Among them, it is preferable to use a container rotation type dryer because it causes less mechanical damage. For a description of specific devices and the like, reference can be made to WO 2018 / 092863 and WO 2018 / 092864. When using an indirect heating type drying device as described above, the material to be dried may be heated by heating a jacket or a heating tube provided in the drying device with a heat medium, and the temperature of the heat medium is preferably, in order of temperature, more than 160°C, more than 160°C and not more than 250°C, 170 to 220°C, 170 to 200°C, 180 to 200°C, and more than 180°C and not more than 200°C.

[0118] In the present invention, during or after the drying step, the hydrogel crosslinked polymer or the dried polymer is heated so that its maximum temperature (hereinafter also simply referred to as maximum temperature) exceeds 160°C.

[0119] In one embodiment, the maximum temperature of the hydrogel crosslinked polymer in the drying step is a temperature exceeding 160°C (form A). In the drying step, if the maximum temperature of the hydrogel crosslinked polymer is 160°C or less, the absorbency of the obtained water-absorbent resin without pressure is low. This makes it necessary to reduce the amount of the internal crosslinking agent used in order to obtain a water-absorbent resin with a high absorbency without pressure, which causes problems such as adhesion of the hydrogel to the device. The maximum temperature of the water-absorbent resin during drying is preferably more than 160°C and not more than 250°C, more preferably 170 to 220°C, and most preferably 170 to 200°C, 180 to 200°C, or more than 180°C and not more than 200°C. If the heat medium temperature or the maximum temperature is 250°C or less, deterioration of the water-absorbent resin during drying is prevented. The maximum temperature of the water-absorbent resin during drying is measured by a contact thermometer installed in the drying device. Examples of the contact thermometer include a thermocouple, a platinum temperature detector, or a bimetal thermometer, particularly a thermocouple (e.g., a K-wire sheathed thermocouple). Typically, the drying temperature is measured at the center of the material layer (particulate hydrous gel or particulate dried material) (e.g., at a position about 5 cm deep when the material has a thickness of 10 cm).

[0120] The drying conditions other than the drying temperature, such as the hot air speed and drying time, may be appropriately set depending on the water content and total weight of the (particulate) hydrogel to be dried and the desired resin solid content. When band drying is performed, the conditions described in WO 2006 / 100300, WO 2011 / 025012, WO 2011 / 025013, WO 2011 / 111657, etc. are appropriately applied.

[0121] The drying time is, for example, preferably 10 to 120 minutes, more preferably 20 to 60 minutes, from the viewpoint of the water absorption capacity (CRC) and the residual monomer.

[0122] [2-5] Grinding process, classification process This step is a step of pulverizing the dried polymer obtained in the above drying step (pulverizing step) and adjusting the particle size to a predetermined range (classifying step) to obtain a water absorbent resin powder (a powdered water absorbent resin before surface crosslinking is conveniently referred to as "water absorbent resin powder").

[0123] Examples of the equipment used in the pulverization step include high-speed rotary pulverizers such as roll mills, hammer mills, screw mills, and pin mills, vibration mills, knuckle-type pulverizers, cylindrical mixers, etc., which are used in combination as necessary. Note that this pulverization step differs from the above-mentioned gel-crushing step in that the dried polymer to be pulverized is subjected to a drying step.

[0124] In addition, the method of adjusting the particle size in the classification step is not particularly limited, but examples thereof include sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)) and air flow classification. The particle size adjustment of the water absorbent resin is not limited to the above-mentioned pulverization step and classification step, and can be appropriately performed in a polymerization step (particularly, reversed-phase suspension polymerization or spray droplet polymerization) or other steps. It is also possible to remove non-standard products (for example, fine powder) classified in the classification step, and the non-standard products may be recycled during the manufacturing process, for example, by granulation.

[0125] The particle size of the water absorbent resin powder obtained in the above step (water absorbent resin powder before the surface crosslinking step, so-called base polymer or water absorbent resin powder after surface crosslinking or addition of additives which is optionally performed, particularly water absorbent resin powder as a final product) is preferably 200 to 600 μm, more preferably 200 to 550 μm, and further preferably 250 to 500 μm as a mass average particle diameter (D50). In addition, the ratio of particles having a particle diameter of 45 μm or more and less than 150 μm (particles which pass through a sieve with a mesh size of 150 μm and do not pass through a sieve with a mesh size of 45 μm in a JIS standard sieve (JIS Z8801-1 (2000))) is preferably 10 mass% or less, more preferably 5 mass% or less, and further preferably 3 mass% or less. The ratio of particles having a particle diameter of 850 μm or more (particles that do not pass through a JIS standard sieve (JIS Z8801-1 (2000)) with an opening of 850 μm) is preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 1 mass% or less. In any case, the lower limit of the ratio of these particles is preferably as low as possible, and 0 mass% is desirable, but it may be about 0.1 mass%. Furthermore, the logarithmic standard deviation (σζ) of the particle size distribution is preferably 0.20 to 0.50, more preferably 0.25 to 0.40, and even more preferably 0.27 to 0.35. These particle sizes are measured using standard sieves in accordance with the measurement methods disclosed in U.S. Pat. No. 7,638,570 and NWSP 220.0.R2(15).

[0126] The above-mentioned particle size is applied not only to the water absorbent resin after surface cross-linking (hereinafter, for convenience, may be referred to as "water absorbent resin particles") but also to the water absorbing agent as a final product. Therefore, in the water absorbent resin particles, it is preferable to carry out a surface cross-linking treatment (surface cross-linking step) so as to maintain the particle size in the above range, and the particle size may be adjusted by providing a sizing step (pulverization, classification step) after the surface cross-linking step.

[0127] [2-6] Surface crosslinking process This step is a step of providing a portion with higher crosslink density on the surface layer of the water absorbent resin powder (a portion several tens of μm from the surface of the water absorbent resin powder), and is composed of a mixing step, a heat treatment step, and a cooling step (optional).

[0128] In the surface cross-linking step, a surface-cross-linked water-absorbent resin (water-absorbent resin particles) is obtained by radical cross-linking or surface polymerization on the surface of the water-absorbent resin powder, a cross-linking reaction with a surface cross-linking agent, or the like. From the viewpoint of water absorption performance such as weighted water absorption ratio, it is preferable to perform surface cross-linking. The surface cross-linking step may be performed simultaneously with the drying step of [2-4], with reference to the descriptions in WO 2018 / 092863, WO 2014 / 038324, and the like.

[0129] [2-6-1: Mixing process] This step is a step of mixing a water-absorbent resin powder or a hydrogel-like crosslinked polymer with a surface crosslinking agent. The method of mixing the surface crosslinking agent is not particularly limited, but includes a method of preparing a surface crosslinking agent solution in advance, and preferably spraying or dropping the liquid onto the water-absorbent resin powder or the hydrogel-like crosslinked polymer, more preferably spraying and mixing.

[0130] The surface cross-linking agent is not particularly limited, but may be an organic or inorganic surface cross-linking agent. Among them, from the viewpoint of the physical properties of the water-absorbent resin and the handling of the surface cross-linking agent, an organic surface cross-linking agent that reacts with a carboxyl group is preferred. For example, one or more surface cross-linking agents disclosed in U.S. Patent No. 7,183,456 may be mentioned. More specifically, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyvalent amine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, etc. may be mentioned.

[0131] Specific examples of organic surface crosslinking agents include polyalcohol compounds such as (di, tri, tetra, poly)ethylene glycol, (di, poly)propylene glycol, 1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, (poly)glycerin, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, trimethylolpropane, di- or triethanolamine, pentaerythritol, and sorbitol; epoxy compounds such as (poly)ethylene glycol diglycidyl ether, (di, poly)glycerol polyglycidyl ether, and glycidol; and 2-oxazolidone. oxazoline compounds such as 1,3-dioxolan-2-one (ethylene carbonate), 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 4-hydroxymethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4-methyl-1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one, 1,3-dioxopan-2-one, and the like.

[0132] In addition to the above organic surface cross-linking agents, polyvalent cationic polymers such as polyamine polymers and water-soluble polyvalent metal cation-containing compounds may be used in combination as ion-bonding surface cross-linking agents.

[0133] The amount of the surface crosslinking agent used (the total amount used when a plurality of agents are used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, based on 100 parts by mass of the water-absorbent resin powder or the water-containing gel-like crosslinked polymer (solid content). The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the water-absorbent resin powder or the water-containing gel-like crosslinked polymer (solid content). Furthermore, when a hydrophilic organic solvent is used as necessary, the amount used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the water-absorbent resin powder or the water-containing gel-like crosslinked polymer (solid content).

[0134] As described above, in the surface cross-linking step, a water-soluble polyvalent metal cation-containing compound may be added.

[0135] [2-6-2: Heat treatment process] This step is a step of applying heat to the mixture discharged from the mixing step to cause a crosslinking reaction on the surface of the water absorbent resin powder. This step may be performed simultaneously with the drying step, or may be performed after the drying step.

[0136] The device for carrying out the crosslinking reaction is not particularly limited. When the crosslinking reaction is carried out in the drying step, the device for carrying out the crosslinking reaction is a drying device, and when the water absorbent resin powder after drying is subjected to a heat treatment, a paddle dryer is preferably used. The reaction temperature in the crosslinking reaction is appropriately set depending on the type of the surface crosslinking agent used, and is preferably 50 to 300°C, more preferably 100 to 200°C.

[0137] In the present invention, as described above, the hydrogel crosslinked polymer or the dried polymer is heated during or after the drying step so that the maximum temperature reaches exceeds 160°C. If the maximum temperature reaches of the hydrogel crosslinked polymer during the drying step does not exceed 160°C, the hydrogel crosslinked polymer may be heated in the heat treatment step or the subsequent step so that the maximum temperature reaches of the dried polymer exceeds 160°C (form B). Furthermore, in a preferred embodiment, the dried polymer is heated in the surface crosslinking step after the drying step so that the maximum temperature reaches exceeds 160°C. If the drying temperature is 160°C or lower, the absorbency of the obtained water-absorbent resin without pressure is low. This makes it necessary to reduce the amount of the internal crosslinking agent used in order to obtain a water-absorbent resin with a high absorbency without pressure, which causes problems such as adhesion of the hydrogel to the device. The maximum temperature is preferably more than 160°C and not more than 250°C, more preferably 170 to 220°C, still more preferably 170 to 200°C, 180 to 200°C, and most preferably more than 180°C and not more than 200°C. The maximum temperature is measured by a contact thermometer installed in the heating device that performs heating. Examples of the contact thermometer include a thermocouple, a platinum temperature detector, or a bimetal thermometer, and in particular a thermocouple (for example, a K-wire sheathed thermocouple).

[0138] [2-6-3: Cooling process] This step is an optional step which is performed as necessary after the heat treatment step.

[0139] The cooling device is not particularly limited, but is preferably a device having the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The water-absorbent resin particles obtained in the heat treatment step are forcibly cooled, if necessary, to preferably 40 to 80°C, more preferably 50 to 70°C in the cooling step.

[0140] [2-7] Sizing process This step is a step of adjusting the particle size of the surface-crosslinked (particulate) dried polymer. By carrying out the particle size regulation step after the surface-crosslinking step, a water absorbent resin powder having a highly controlled particle size or particle size distribution can be obtained.

[0141] Preferably, the sizing step includes a pulverization step and / or a classification step. The pulverization step and the classification step are the same as those described above. Crushing The process and classification process are the same as those described in the section.

[0142] From the viewpoint of water absorption performance, the particle size of the water absorbent resin powder obtained through the particle regulating step is within the above range.

[0143] [2-8] Addition process of other additives This step is an optional step carried out for the purpose of imparting various additional functions to the water-absorbent resin and improving the water-absorption performance.

[0144] Examples of other additives include chelating agents, organic reducing agents, inorganic fine particles, polyvalent metal salts, inorganic reducing agents, oxidizing agents, hydroxycarboxylic acid compounds, surfactants, compounds having phosphorus atoms, organic powders such as metal soaps, deodorants, antibacterial agents, pulp, thermoplastic fibers, etc. In addition, liquid permeability is one example of the water absorption performance imparted to the water absorbent resin, and additives for improving the liquid permeability include the following polyvalent metal salts, cationic polymers, and inorganic fine particles, and it is preferable to use at least one of these. The amount of these additives to be added is preferably less than 2.0 parts by mass, more preferably less than 1.5 parts by mass, and even more preferably less than 1.0 part by mass, relative to 100 parts by mass of the water absorbent resin powder.

[0145] [2-9] Other processes In addition to the above-mentioned steps, the production method according to the present invention may further include a cooling step, a rewetting step, a pulverizing step, a classification step, a fine powder granulation step, a transporting step, a storing step, a packaging step, a storage step, and the like, as necessary.

[0146] In addition, hydrogen peroxide may be added in the fine powder granulation step (form 4), and the amount of hydrogen peroxide added is preferably 50 ppm (0.005 mass%) to 10000 ppm (1.0 mass%), more preferably 100 ppm (0.01 mass%) to 5000 ppm (0.5 mass%) based on the solid content mass of the hydrogel crosslinked polymer. In addition, any one or more of forms 1 to 3 may be combined, and form 4 is more preferably performed in combination with any one or more of forms 1 to 3. This can sufficiently increase the CRC of the obtained water absorbent resin. In this case, the amount of hydrogen peroxide added is appropriately adjusted so that the amount of hydrogen peroxide is 50 ppm or more based on the solid content mass of the hydrogel crosslinked polymer.

[0147] In the fine powder granulation process, the fine powder classified in the manufacturing process or the fine powder obtained in the above-mentioned granulation process is granulated. The granulated material obtained in this process is preferably recycled during the manufacturing process.

[0148] Granulation is the process of forming particles larger than the original particles by adhering them to each other using physical or chemical techniques.

[0149] The granulation is preferably performed by granulation using a solvent such as water or a hydrophilic solvent. Examples of the solvent include water; alcohols such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and t-butyl alcohol; and combinations thereof. The solvent is preferably water. The amount of the solvent depends on the moisture content of the fine powder used, but is usually in the range of 25 to 250 parts by mass, preferably 25 to 200 parts by mass, relative to 100 parts by mass of the solid content of the water absorbent resin.

[0150] The device used when mixing the solvent and the fine powder is not particularly limited. For example, if the container is a fixed type mixer, a mechanical stirring type mixer is preferable. Specific examples include Turbulizer (manufactured by Hosokawa Micron Corporation), Loedige Mixer (manufactured by Loedige Corporation), and Mortar Mixer (manufactured by Nishinippon Shikenki Co., Ltd.). In addition, either a batch type mixer or a continuous type mixer may be used for mixing.

[0151] The heating temperature of the inside of the mixing device, preferably the inner wall surface of the mixing device and / or the stirring means during the above mixing is preferably 60°C or higher, more preferably 65°C or higher, even more preferably 70°C or higher, and preferably 120°C or lower, more preferably 100°C or lower, even more preferably 90°C or lower. By heating the mixer device (preferably either the inner wall surface or the stirring means, more preferably both), the fine powder can be uniformly granulated in a short time, improving productivity. The temperature inside the mixing device can be appropriately adjusted, for example, by supplying heated gas or by conductive heat transfer.

[0152] When hydrogen peroxide is added in this step, the method of adding hydrogen peroxide is not particularly limited, but it is preferable to add hydrogen peroxide as an aqueous solution in which hydrogen peroxide is dissolved, using water as the solvent, because it is easy to add hydrogen peroxide. In addition, the granulated product to which hydrogen peroxide is added obtained in this step is preferably recycled during the manufacturing process, and is preferably heated to a temperature exceeding 160°C after the addition. Specifically, the granulated product to which hydrogen peroxide is added can be added in the steps of preparing a monomer composition; the polymerization step (for example, in the form of adding hydrogen peroxide to a gel during or after polymerization, or in the crushing step); the gel crushing step; the drying step; and the mixing step of a surface crosslinking agent. When recycling, the water absorbent resin granulated product may be preferably dried and crushed, but is preferably recycled as a granulated product (granulated gel) mixed with an aqueous liquid (preferably water).

[0153] [3. Properties of the obtained water-absorbent resin] The present invention also provides a water-absorbing resin obtained by the manufacturing method of the above embodiment. The physical properties of the water-absorbing resin are preferably as follows. The following physical property values ​​are also applicable as a water-absorbing agent (a water-absorbing resin composition that may contain a water-absorbing resin and other components) within a suitable range.

[0154] [3-1] CRC (Water absorption capacity without pressure, centrifuge holding capacity) "CRC" is an abbreviation for Centrifuge Retention Capacity, and means the water absorption capacity of a water-absorbent resin under no pressure (sometimes referred to as "water absorption capacity").

[0155] The CRC of the water-absorbent resin is usually 5 g / g or more, preferably 15 g / g or more, more preferably 25 g / g or more, 30 g / g or more, 35 g / g or more, 40 g / g or more, or even 45 g / g or more, 50 g / g or more. The upper limit is not particularly limited, and a higher CRC is preferable, but from the viewpoint of balance with other physical properties, it is preferably 70 g / g or less, more preferably 65 g / g or less. In the present invention, the water-absorbent resin having a high water-absorbency capacity (CRC) before surface crosslinking of 30 g / g or more, 35 g / g or more, 40 g / g or more, or even 45 g / g or more, 50 g / g or more, or 55 g / g or more can be suitably applied to the production of the water-absorbent resin having a high water-absorbency capacity before surface crosslinking, and a water-absorbent resin having a high water-absorbency capacity, which was previously difficult to produce due to the adhesion of the hydrous gel, can be easily produced.

[0156] If the CRC is less than 5 g / g, the absorption capacity is low and the absorbent is not suitable for use in absorbent articles such as paper diapers. If the CRC is more than 70 g / g, the rate at which the absorbent absorbs body fluids such as urine and blood is reduced, making the absorbent unsuitable for use in paper diapers with high water absorption rates. According to the present production method, a water-absorbent resin with a high CRC can be obtained.

[0157] In the present invention, the CRC of the water-absorbing resin is preferably larger than the CRC of the (particulate) hydrogel in terms of reducing adhesion to the polymerization apparatus, reducing the load on the crushing apparatus, and water-absorbing properties. Specifically, the CRC (g / g) of the water-absorbing resin minus the CRC (g / g) of the (particulate) hydrogel is preferably 5 g / g or more, 8 g / g or more, 10 g / g or more, 15 g / g or more, and 17 g / g or more in this order. The upper limit of the CRC (g / g) of the water-absorbing resin minus the CRC (g / g) of the (particulate) hydrogel is, for example, 30 g / g or less.

[0158] [3-2] AAP (absorption capacity under pressure) The AAP (absorption capacity under pressure) of the water-absorbent resin is preferably 15 g / g or more, more preferably 20 g / g or more, even more preferably 23 g / g or more, particularly preferably 24 g / g or more, and most preferably 25 g / g or more. The upper limit is not particularly limited, but is preferably 40 g / g or less.

[0159] [3-3] Residual amount of hydrogen peroxide The residual amount of hydrogen peroxide in the water absorbent resin is preferably 10 ppm or less, more preferably 1 ppm or less, and most preferably 0 ppm (below the detection limit). When the residual amount of the added hydrogen peroxide is below the above upper limit, the influence on the water absorption properties of the water absorbent resin is small, and safety is excellent.

[0160] [4] Uses of water-absorbent resins The use of the water-absorbing resin is not particularly limited, but it is preferably used as an absorbent for absorbent articles such as paper diapers (for infants and adults), sanitary napkins, and incontinence pads. In particular, it can be used as an absorbent for high-concentration paper diapers. Examples of other absorbent articles include drip absorbents, freshness-preserving materials, emergency toilets, pet sheets, and cat litter. Other uses of water-absorbent resins include soil water retention agents, seedling sheets, seed coating materials, condensation prevention sheets, disposable hand warmers, cooling bandanas, ice packs, medical waste liquid solidification agents, residual soil solidification materials, water damage prevention waste liquid gelling agents, water-absorbing sandbags, poultice materials, thickeners for cosmetics, water-stopping materials for electric and electronic materials and communication cables, gasket packing, sustained-release agents for fertilizers, various sustained-release agents (space disinfectants, air fresheners, etc.), wound protection dressing materials, condensation prevention building materials, oil moisture removers, paints, adhesives, anti-blocking agents, light diffusing agents, matting agents, additives for decorative panels, additives for artificial marble, additives for toners, and other resin additives.

[0161] In addition, as the raw material of the absorbent body, an absorbent material such as pulp fiber can be used together with the water-absorbent resin. In this case, the content (core concentration) of the water-absorbent resin in the absorbent body is preferably 30% by mass to 100% by mass, more preferably 40% by mass to 100% by mass, even more preferably 50% by mass to 100% by mass, even more preferably 60% by mass to 100% by mass, particularly preferably 70% by mass to 100% by mass, and most preferably 75% by mass to 95% by mass.

[0162] By setting the core concentration within the above range, when the absorbent is used in the upper layer of an absorbent article, the absorbent article can be maintained in a clean white state. Furthermore, since the absorbent has excellent diffusibility of body fluids such as urine and blood, efficient liquid distribution is achieved, and an improvement in the absorption amount can be expected.

[0163] [3-5] Comparison with conventional technology As disclosed in Patent Documents 8, 13, and 14, the use of hydrogen peroxide as a polymerization initiator is also known. However, for example, Patent Document 8 (long-term reversed-phase suspension polymerization) and Patent Documents 13 and 14 (long-term redox polymerization) do not suggest the amount of hydrogen peroxide remaining in the polymer after polymerization or the present production method and its problematic effects caused by heating at above 160°C. EXAMPLES

[0164] The present invention will be described in more detail with reference to the following experimental examples. However, the present invention is not limited to these explanations, and experimental examples obtained by appropriately combining the technical means disclosed in each experimental example are also included in the scope of the present invention.

[0165] In addition, the term "water-absorbent resin" described below means a granular dried material that has been subjected to a drying process, a surface-crosslinked granular dried material or a water-absorbent resin powder, and a surface-crosslinked water-absorbent resin powder, and the term "water-containing gel" means a water-containing gel-like crosslinked polymer or a particulate water-containing gel-like crosslinked polymer that has not been subjected to a drying process.

[0166] In addition, unless otherwise noted, electric devices (including devices for measuring the physical properties of the water-absorbent resin) used in the experimental examples were powered by a 60 Hz, 200 V or 100 V power source. In addition, unless otherwise noted, the various physical properties of the water-absorbent resin and the hydrous gel described below were measured under the conditions of room temperature (20°C to 25°C) and a relative humidity of 50% RH ± 10%.

[0167] For convenience, "liter" may be expressed as "l" or "L", and "mass%" or "weight%" as "wt%". When measuring trace components, amounts below the detection limit may be expressed as ND (Non Detected).

[0168] [Example 1] Addition of hydrogen peroxide to a polymerization process of high concentration / high temperature start / short time polymerization (first and second methods of the present invention) A 2-liter polypropylene container was charged with 422.0 g (5.86 mol) of acrylic acid, 11.94 g (0.039 mol % relative to the monomer) of a 10 mass % aqueous solution of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.29 g (0.00096 mol % relative to the monomer) of a 2.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 173.9 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 394.6 g of deionized water (ion-exchanged water) and mixed to prepare a monomer composition (a1).

[0169] Next, the monomer composition (a1) was cooled while stirring. When the liquid temperature reached 42°C, 178.7g of 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to produce a monomer composition (a2) (neutralization rate of acrylic acid: 73% by mole). At this time, the temperature of the monomer composition (a2) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but the precipitates gradually dissolved to form a transparent homogeneous solution.

[0170] Next, 1.0 g of 5.0 mass% aqueous hydrogen peroxide solution (100 ppm hydrogen peroxide relative to the solid content in the monomer composition (total amount of monomer, acrylic acid, and sodium acrylate)) and 16.5 g of 4.5 mass% aqueous sodium persulfate solution (0.053 mol% relative to monomer) were added to the stirred monomer composition (a2) (78°C) to obtain a monomer composition (a'2). Thereafter, the monomer composition (a'2) (monomer concentration 43 mass%, neutralization rate of acrylic acid 73 mol%) was immediately poured into a stainless steel bat-shaped container (bottom 340 x 340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-to-air system. The time from the start of the second stage neutralization to pouring the monomer composition (a'2) into the vat-shaped container was 1 minute, and the vat-shaped container was heated using a hot plate (NEO HOTPLATE HI-1000 / Iuchi Seieido Co., Ltd.) until the surface temperature reached 50° C. The time from when the temperature of the monomer composition began to rise (from the start of polymerization) to when it reached the maximum temperature (over 100° C.) was 1 minute.

[0171] In the above, the monomer is composed of acrylic acid and sodium acrylate produced by neutralizing acrylic acid and sodium hydroxide, and the sum of the contents of these is the monomer content in the calculation of the monomer concentration.

[0172] The hydrogel (a3) ​​(about 65°C) obtained by the above polymerization reaction (monomer concentration 43% by mass, monomer temperature at the start of polymerization 78°C, polymerization time 1 minute → high concentration / high temperature start / short time polymerization) was crushed immediately after polymerization (within 5 minutes after removal from the polymerization machine) using a meat chopper (manufactured by Remacom Co., Ltd., model: HL-G22SN) equipped with a 9.5 mm die diameter plate to obtain a particulate hydrogel (b1). The amount of the hydrogel (a3) ​​fed into the meat chopper was 375 g / min, and in parallel with the feeding of the hydrogel (a3), 25°C deionized water was fed into the meat chopper at 50 g / min to perform gel crushing, thereby obtaining a particulate hydrogel (b1). The obtained particulate hydrogel (b1) had a mass average particle diameter calculated on solid content (hereinafter simply referred to as gel particle diameter) of 600 μm, a CRC of 34.2 g / g, and a hydrogen peroxide content of 70 ppm (70% of the hydrogen peroxide added in the polymerization step). The gel solid content of the obtained particulate hydrogel (b1) was 46.0% by mass.

[0173] This finely divided particulate hydrogel (b1) (approximately 60°C) was spread on a 50-mesh wire net and subjected to static hot air drying at 190°C for 30 minutes. Continuous operation was performed within 30 minutes from the end of polymerization to the start of drying, including gel crushing. When a K-wire sheathed thermocouple (manufactured by Asahi Sangyo Co., Ltd., TS4-K16CS-U-300-WXA3000) was placed in the center of the material layer (particulate hydrogel and granular dried material) and measured, the maximum temperature reached (hereinafter, the maximum temperature reached by the hydrogel-like crosslinked polymer is also simply referred to as the drying temperature) was 190°C.

[0174] The dried product was pulverized using a roll mill (WML type roll pulverizer / Inoguchi Giken Co., Ltd.), and further sieved using JIS sieves having mesh sizes of 850 μm and 150 μm. Particles that did not pass through the 850 μm sieve and particles that passed through the 150 μm sieve were removed, thereby obtaining an irregularly pulverized water absorbent resin (c1).

[0175] The resin solid content of the obtained water absorbent resin (c1) was 96.0% by mass. In addition, the particle size distribution of the water absorbent resin (c1) was 3% by mass of particles that passed 850 μm but did not pass 600 μm, 10% by mass of particles that passed 600 μm but did not pass 500 μm, 54% by mass of particles that passed 500 μm but did not pass 300 μm, 31% by mass of particles that passed 300 μm but did not pass 150 μm, and 2% by mass of particles that passed 150 μm but did not pass 45 μm. The mass average particle diameter D50 was 346 μm, σζ was 0.355, and CRC was 56.3 g / g (CRC increase from the hydrogel before drying = +22.1 g / g), and hydrogen peroxide was not detected.

[0176] [Example 2] Changing the amount of hydrogen peroxide (100 ppm → 200 ppm) The same operations as in Example 1 were carried out except that the amount of the aqueous hydrogen peroxide solution used in preparing the monomer composition in Example 1 was changed to 2.1 g (200 ppm of hydrogen peroxide relative to the solid content (monomer) in the monomer composition) and the amount of deionized water was changed to 393.6 g, and a particulate hydrogel (b2) was obtained by polymerization of a monomer composition having a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%.

[0177] The obtained particulate hydrogel (b2) had a gel particle size of 620 μm, a CRC of 33.5 g / g, a gel solid content of 46.8 mass%, and a hydrogen peroxide content of 165 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (c2) had a CRC of 60.1 g / g (CRC increase from the hydrogel before drying=+26.6 g / g), a solid content of 96.5 mass%, and no hydrogen peroxide was detected.

[0178] [Example 3] Change in the amount of crosslinker and hydrogen peroxide (PEGDA 0.039 → 0.075 mol%, hydrogen peroxide 100 ppm → 800 ppm) The same operations as in Example 1 were carried out except that the amount of deionized water used in preparing the monomer composition in Example 1 was changed to 376.4 g, the amount of polyethylene glycol diacrylate (PEGDA) aqueous solution was changed to 23.0 g (PEGDA=0.075 mol% relative to monomer), and the amount of hydrogen peroxide aqueous solution was changed to 8.3 g (hydrogen peroxide 800 ppm relative to the solid content (monomer) in the monomer composition), and a particulate hydrogel (b3) was obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / neutralization rate of 73 mol%.

[0179] The obtained particulate hydrogel (b3) (PEGDA=0.075 mol%) had a gel particle size of 540 μm, a CRC of 30.0 g / g, a gel solid content of 47.0 mass%, and a hydrogen peroxide content of 680 ppm. After drying at a drying temperature of 190° C., the mixture was sieved in the same manner as in Example 1, and particles that did not pass through an 850 μm sieve and particles (c3′) that passed through a 150 μm sieve were removed to adjust the mass average particle size and its distribution. The obtained water-absorbent resin (c3) had a CRC of 47.7 g / g (CRC increase from the hydrogel before drying=+17.7 g / g), a solid content of 96.8 mass%, and no hydrogen peroxide was detected.

[0180] [Example 4] Change in the amount of crosslinker and hydrogen peroxide (PEGDA 0.039 → 0.12 mol%, hydrogen peroxide 100 ppm → 2000 ppm) The same operations as in Example 1 were carried out except that the amount of deionized water used in preparing the monomer composition in Example 1 was changed to 350.22 g, the amount of the polyethylene glycol diacrylate aqueous solution was changed to 36.8 g (0.12 mol% relative to the monomer), and the amount of the hydrogen peroxide aqueous solution was changed to 20.6 g (2000 ppm of hydrogen peroxide relative to the solid content (monomer) in the monomer composition), and a particulate hydrogel (b4) was obtained by polymerization of a monomer composition having a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%.

[0181] The obtained particulate hydrogel (b4) (PEGDA=0.12 mol%) had a gel particle size of 500 μm, a CRC of 27.8 g / g, a gel solid content of 48.0 mass%, and a hydrogen peroxide content of 1750 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (c4) had a CRC of 49.0 g / g (CRC increase from the hydrogel before drying=+21.2 g / g), a solid content of 97.2 mass%, and no hydrogen peroxide was detected.

[0182] [Example 5] Changing the type and amount of crosslinking agent (PEGDA = 0.039 mol% → TMPTA = 0.026 mol%) The same operations as in Example 1 were carried out except that the amount of acrylic acid used in preparing the monomer composition in Example 1 was changed to 417.9 g, the 10 mass% polyethylene glycol diacrylate aqueous solution was changed to 4.5 g of a 10 mass% trimethylolpropane triacrylate (TMPTA) acrylic acid solution (0.026 mol% TMPTA relative to monomer), and the amount of deionized water was changed to 406.1 g, and a particulate hydrogel (b5) was obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%.

[0183] The obtained particulate hydrogel (b5) (TMPTA=0.026 mol%) had a gel particle size of 610 μm, a CRC of 36.5 g / g, a gel solid content of 46.9 mass%, and a hydrogen peroxide content of 80 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (c5) had a CRC of 46.5 g / g (CRC increase from the hydrogel before drying=+10.0 g / g), a solid content of 96.4 mass%, and no hydrogen peroxide was detected.

[0184] [Example 6] Changing the amount of hydrogen peroxide (100 ppm → 200 ppm) The same operations as in Example 5 were carried out except that the amount of the aqueous hydrogen peroxide solution used in preparing the monomer composition in Example 5 was changed to 2.1 g (200 ppm of hydrogen peroxide relative to the solid content (monomer) in the monomer composition) and the amount of deionized water was changed to 405.1 g, and a particulate hydrogel (b6) was obtained by polymerization of a monomer composition having a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%.

[0185] The obtained particulate hydrogel (b6) had a gel particle size of 580 μm, a CRC of 37.2 g / g, a gel solid content of 48.2 mass%, and a hydrogen peroxide content of 155 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (c6) had a CRC of 53.0 g / g (CRC increase from the hydrogel before drying=+15.8 g / g), a solid content of 96.0 mass%, and no hydrogen peroxide was detected.

[0186] [Example 7] Changes in hydrogen peroxide amount (800 ppm to 1000 ppm) and gel particle size (die hole diameter) The same operations as in Example 3 were carried out except that the amount of deionized water used in preparing the monomer composition in Example 3 was changed to 374.3 g, the amount of the aqueous hydrogen peroxide solution was changed to 10.3 g (1000 ppm of hydrogen peroxide relative to the solid content (monomer) in the monomer composition), and the die diameter of the meat chopper was changed to 3.5 mm, and a particulate hydrogel (b7) was obtained by polymerization of a monomer composition having a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%.

[0187] The obtained particulate hydrogel (b7) had a gel particle size of 200 μm, a CRC of 31.0 g / g, a gel solid content of 47 mass%, and a hydrogen peroxide content of 840 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (c7) had a CRC of 48.0 g / g (CRC increase from the hydrogel before drying=+17.0 g / g), a solid content of 97 mass%, and no hydrogen peroxide was detected.

[0188] [Example 8] Addition of hydrogen peroxide in the gel crushing step after the polymerization step (first and third methods of the present invention) A 2-liter polypropylene container was charged with 422.0 g of acrylic acid, 11.94 g (0.039 mol % relative to the monomer) of a 10 mass % aqueous solution of polyethylene glycol diacrylate (PEGDA) (molecular weight 523) as an internal crosslinking agent, 1.29 g (0.00096 mol % relative to the monomer) of a 2.0 mass % aqueous solution of trisodium diethylenetriaminepentaacetate (DTPA·3Na), 173.9 g of a 48.5 mass % aqueous solution of sodium hydroxide, and 395.7 g of deionized water (ion-exchanged water) and mixed to prepare a monomer composition (a4).

[0189] Next, the monomer composition (a4) was cooled while stirring. When the liquid temperature reached 42°C, 178.7 g of 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to produce a monomer composition (a5). At this time, the temperature of the monomer composition (a5) rose to 78.0°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, a precipitate was observed, but the precipitate gradually dissolved and became a transparent homogeneous solution (a 73 mol% neutralized aqueous sodium acrylate solution (about 78°C) containing 0.039 mol% PEGDA).

[0190] Next, 16.5 g of a 4.5% by mass aqueous solution of sodium persulfate was added to the monomer composition (a5) in a stirred state, and the mixture (monomer composition (a'5) monomer concentration 43% by mass / acrylic acid neutralization rate 73%) was immediately poured into a stainless steel bat-shaped container (bottom 340 x 340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-to-air system. The time from the start of the second stage neutralization to pouring the monomer composition (a'5) into the bat-shaped container was 1 minute, and the bat-shaped container was heated to a surface temperature of 50°C using a hot plate (NEO HOTPLATE HI-1000 / Iuchi Seiei-do Co., Ltd.). The time from when the temperature of the monomer composition started to rise to when it reached the maximum temperature was 1 minute.

[0191] The hydrogel (a6) obtained by the above polymerization reaction (monomer concentration 43% by mass, monomer temperature at the start of polymerization 78°C, polymerization time 1 minute → high concentration / high temperature start / short time polymerization, no hydrogen peroxide used) was crushed using a meat chopper (manufactured by Remacom Co., Ltd., model: HL-G22SN) equipped with a 9.5 mm die aperture plate, to obtain a particulate hydrogel (b8).

[0192] The hydrous gel (a6) (solid content rate of 53.0% by mass) was fed to the meat chopper at a rate of 375 g / min, and in parallel with the feeding of the hydrous gel (a6), a 0.08% by mass aqueous hydrogen peroxide solution at 25° C. was fed to the meat chopper at a rate of 50 g / min (corresponding to 200 ppm of hydrogen peroxide relative to the solid content of the hydrous gel (a6)) to crush the gel, thereby obtaining a particulate hydrous gel (b8). The obtained particulate hydrous gel (b8) had a gel particle size of 600 μm, a CRC of 34.0 g / g, a gel solid content rate of 46.8% by mass, and a hydrogen peroxide content of 180 ppm.

[0193] This finely divided hydrogel (b8) was spread on a 50-mesh wire net immediately after crushing the gel (within 5 minutes) in the same manner as in Examples 1 to 7 above, and was subjected to stationary hot air drying at 190°C for 30 minutes. The K-wire sheathed thermocouple was placed in the center of the material layer and measured, and the maximum temperature reached (drying temperature) was 190°C. The dried product was pulverized using a roll mill in the same manner as in Examples 1 to 7 above, and further sieved using JIS sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly crushed water-absorbent resin (c8).

[0194] The resin solid content of the obtained water absorbent resin (c8) was 96.3% by mass. The particle size distribution of the water absorbent resin (c8) was 3% by mass of particles that passed 850 μm but did not pass 600 μm, 10% by mass of particles that passed 600 μm but did not pass 500 μm, 54% by mass of particles that passed 500 μm but did not pass 300 μm, 31% by mass of particles that passed 300 μm but did not pass 150 μm, and 2% by mass of particles that passed 150 μm but did not pass 45 μm. The mass average particle diameter D50 was 346 μm, σζ was 0.355, and CRC was 61.0 g / g (CRC increase from the hydrous gel before drying = +27.0 g / g), and hydrogen peroxide was not detected.

[0195] [Example 9] Change in the amount of crosslinker and hydrogen peroxide (PEGDA 0.039 → 0.12 mol%, hydrogen peroxide 200 ppm → 2000 ppm) The same operations as in Example 8 were carried out except that the amount of 10 mass% polyethylene glycol diacrylate (PEGDA) aqueous solution was changed to 36.75 g (0.12 mol% relative to the monomer), the amount of deionized water (ion-exchanged water) was changed to 370.9 g, and the 0.08 mass% hydrogen peroxide aqueous solution was changed to 0.8 mass% hydrogen peroxide aqueous solution (equivalent to 2000 ppm relative to the solid content of the hydrous gel (b9)), and a particulate hydrous gel (b9) was obtained by polymerization from a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%.

[0196] The obtained particulate hydrogel (b9) (PEGDA=0.12 mol%) had a gel particle size of 510 μm, a CRC of 28.0 g / g, a gel solid content of 47.1 mass%, and a hydrogen peroxide content of 1820 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Examples 1 to 8, and the obtained water absorbent resin (c9) had a CRC of 49.3 g / g (CRC increase from the hydrogel before drying=+21.3 g / g), a solid content of 97.3 mass%, and no hydrogen peroxide was detected.

[0197] [Example 10] Changing the type and amount of crosslinker (PEGDA = 0.039 → TMPTA = 0.026 mol%) The same operations as in Example 8 were carried out except that the amount of acrylic acid used was changed to 417.9 g, the 10 mass% polyethylene glycol diacrylate (PEGDA) aqueous solution was changed to 4.5 g of a 10 mass% trimethylolpropane triacrylate (TMPTA) acrylic acid solution (0.026 mol% relative to the monomer), and the amount of deionized water (ion-exchanged water) was changed to 407.2 g, and a particulate hydrogel (b10) was obtained by polymerization from a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%.

[0198] The obtained particulate hydrogel (b10) had a gel particle size of 590 μm, a CRC of 36.3 g / g, a gel solid content of 47.2 mass%, and a hydrogen peroxide content of 165 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Examples 1 to 9, and the obtained water absorbent resin (c10) had a CRC of 53.2 g / g (CRC increase from the hydrogel before drying=+16.9 g / g), a solid content of 96.2 mass%, and no hydrogen peroxide was detected.

[0199] [Example 11] Change in hydrogen peroxide amount (2000 ppm → 2500 ppm) and gel particle size (die hole diameter 9.5 → 3.5 mm) The same procedure as in Example 9 was carried out, except that the die diameter of the meat chopper was changed to 3.5 mm and the 0.8% by mass hydrogen peroxide aqueous solution was changed to a 1.0% by mass hydrogen peroxide aqueous solution (equivalent to 2500 ppm relative to the solid content of the hydrous gel (b11)), to obtain a particulate hydrous gel (b11).

[0200] The obtained particulate hydrogel (b11) had a gel particle size of 180 μm, a CRC of 29.0 g / g, a gel solid content of 47.5 mass%, and a hydrogen peroxide content of 2300 ppm. After drying at a drying temperature of 190° C., the mass average particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (c11) had a CRC of 49.5 g / g (CRC increase from the hydrogel before drying=+20.5 g / g), a solid content of 97.6 mass%, and no hydrogen peroxide was detected.

[0201] [Example 12] Addition of hydrogen peroxide to fine granulated powder 300g of particles (c3') (CRC = 42g / g) that passed through 150μm obtained by repeating Example 3 multiple times was placed in a 5L mortar mixer (manufactured by Nishinippon Shikenki Seisakusho) kept warm in a water bath at 80℃, and while rotating the stirring blade of the mortar mixer at high speed at 60Hz / 100V, 320g of 0.2% hydrogen peroxide aqueous solution at 80℃ (318g of deionized water at 80℃ and 1.8g of 36% hydrogen peroxide aqueous solution were mixed and used within 1 minute after mixing) was added all at once. The hydrogen peroxide aqueous solution was mixed with the fine powder water absorbent resin (c3') within 10 seconds of being added to form a granule, which was taken out after mixing for 1 minute, and a granulated gel (g1) (CRC = 42g / g) with a particle size of 3 to 10mm was obtained. The solid content of the granulated gel (g1) was 47% by mass, and the amount of hydrogen peroxide was 2000ppm.

[0202] Next, 1600 g of the particulate hydrogel (b3) obtained in Example 3 and 300 g of the granulated gel (g1) were mixed to obtain a hydrogel (b12). The particulate hydrogel (b3) and the granulated gel (g1) were mixed immediately (within 5 minutes) after the gel was crushed and granulated. The hydrogel (b12) had a CRC of 31.9 g / g, a gel solid content of 47.0 mass%, and a hydrogen peroxide content of 890 ppm.

[0203] The obtained hydrous gel (b12) was spread on a 50-mesh wire net immediately after mixing (within 5 minutes) in the same manner as in Examples 1 to 11 above, and was subjected to static hot air drying at 190°C for 30 minutes. The K-wire sheathed thermocouple was placed at the center of the material layer and measured, and the maximum temperature reached (drying temperature) was 190°C. The dried product was pulverized using a roll mill in the same manner as in Examples 1 to 11 above, and further sieved using JIS sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water absorbent resin (c12). The resin solid content of the obtained water absorbent resin (c12) was 96.3 mass%. The particle size distribution of the water-absorbent resin (c12) was 3 mass% of particles that passed 850 μm but did not pass 600 μm, 10 mass% of particles that passed 600 μm but did not pass 500 μm, 54 mass% of particles that passed 500 μm but did not pass 300 μm, 31 mass% of particles that passed 300 μm but did not pass 150 μm, and 2 mass% of particles that passed 150 μm but did not pass 45 μm. The mass average particle diameter D50 was 346 μm, σζ was 0.355, and CRC was 49.0 g / g (CRC increase from the hydrous gel before drying = +17.1 g / g). No hydrogen peroxide was detected.

[0204] Example 13 Change in drying conditions (190℃, 30 minutes → 170℃, 40 minutes) The same operation as in Example 1 was performed except that the drying of the hydrogel was changed to 170 ° C. and 40 minutes, and a particulate hydrogel (b13) and a water-absorbent resin (c13) were obtained. The particulate hydrogel (b13) obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol% had a gel particle size of 590 μm, a CRC of 34.0 g / g, a gel solid content of 46.0 mass%, and a hydrogen peroxide content of 80 ppm. The particulate hydrogel (b13) was dried, and the maximum temperature reached by the material during drying (drying temperature) was 170 ° C. The particle size and distribution of the dried product were adjusted in the same manner as in Example 1, and the CRC of the obtained water-absorbent resin (c13) was 53.0 g / g (CRC increase from the hydrogel before drying = +19 g / g), the solid content was 96.0 mass%, and hydrogen peroxide was not detected.

[0205] [Example 14] Changing the drying conditions (190°C, 30 minutes → 170°C, 40 minutes) The same operation as in Example 8 was performed except that the drying of the hydrogel was changed to 170 ° C. and 40 minutes, and a particulate hydrogel (b14) and a water-absorbent resin (c14) were obtained. The particulate hydrogel (b14) obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol% had a gel particle size of 610 μm, a CRC of 34.3 g / g, a gel solid content of 46.5 mass%, and a hydrogen peroxide content of 175 ppm. The particulate hydrogel (b14) was dried, and the maximum temperature reached by the material during drying (drying temperature) was 170 ° C. The particle size and distribution of the dried product were adjusted in the same manner as in Example 1, and the CRC of the obtained water-absorbent resin (c14) was 55.0 g / g (CRC increase from the hydrogel before drying = +20.7 g / g), the solid content was 96.2 mass%, and hydrogen peroxide was not detected.

[0206] [Comparative Example 1] No hydrogen peroxide, change in drying conditions (190°C, 30 minutes → 150°C, 50 minutes) The same operations as in Example 1 were carried out except that no aqueous hydrogen peroxide solution was used in the polymerization step, the amount of deionized water used in preparing the monomer composition was changed to 395.7 g, and the drying of the hydrogel was changed to 150°C for 50 minutes. A particulate hydrogel (d1) was obtained by polymerization of a monomer composition having a monomer concentration of 43 mass% and an acrylic acid neutralization rate of 73 mol%.

[0207] The obtained particulate hydrogel (d1) had a gel particle size of 610 μm, a CRC of 33.0 g / g, and a gel solid content of 46.3 mass%. The gel was dried at a maximum temperature (drying temperature) of 150° C., and the particle size and distribution of the dried product were adjusted in the same manner as in Example 1. The obtained water-absorbent resin (e1) had a CRC of 35 g / g (CRC increase from the hydrogel before drying=+2 g / g), and a solid content of 95.8 mass%.

[0208] [Comparative Example 2] Change in drying conditions (190°C, 30 minutes → 150°C, 50 minutes) The same operation as in Example 1 was performed except that the drying of the hydrogel was changed to 150 ° C. and 50 minutes, and a particulate hydrogel (d2) was obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%. The obtained particulate hydrogel (d2) had a gel particle size of 600 μm, a CRC of 33.0 g / g, a gel solid content of 47.2 mass%, and a hydrogen peroxide content of 70 ppm. The maximum temperature reached by the material during drying (drying temperature) was 150 ° C. The particle size and distribution of the dried material were adjusted in the same manner as in Example 1, and the CRC of the obtained water-absorbing resin (e2) was 36 g / g (CRC increase from the hydrogel before drying = +3.0 g / g), and the solid content was 95.5 mass%.

[0209] [Comparative Example 3] Change in drying conditions (190°C, 30 minutes → 150°C, 50 minutes) The same operation as in Example 8 was performed except that the drying of the hydrogel was changed to 150 ° C. and 50 minutes, and a particulate hydrogel (d3) and a water-absorbent resin (e3) were obtained. The particulate hydrogel (d3) obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol% had a gel particle size of 600 μm, a CRC of 33.0 g / g, a gel solid content of 46.8 mass%, and a hydrogen peroxide content of 160 ppm. The particulate hydrogel (d3) was dried, and the maximum temperature reached by the material during drying (drying temperature) was 150 ° C. The particle size and distribution of the dried product were adjusted in the same manner as in Example 1, and the CRC of the obtained water-absorbent resin (e3) was 35.5 g / g (CRC increase from the hydrogel before drying = +2.5 g / g), and the solid content was 96.0 mass%.

[0210] [Comparative Example 4] No hydrogen peroxide The same operation as in Example 3 was performed except that no aqueous hydrogen peroxide solution was used in the polymerization step, and the amount of deionized water used in preparing the monomer composition was 384.6 g. A particulate hydrogel (d4) was obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%. The obtained particulate hydrogel (d4) had a gel particle size of 520 μm, a CRC of 29.0 g / g, and a gel solid content of 46.9 mass%. After drying at a drying temperature of 190 ° C., the particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (e4) had a CRC of 36.7 g / g (CRC increase from the hydrogel before drying = +7.7 g / g) and a solid content of 96.9 mass%.

[0211] [Comparative Example 5] No hydrogen peroxide The same operation as in Example 4 was performed except that no aqueous hydrogen peroxide solution was used in the polymerization step, and the amount of deionized water used in preparing the monomer composition was 370.9 g. A particulate hydrogel (d5) was obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%. The obtained particulate hydrogel (d5) had a gel particle size of 490 μm, a CRC of 27.5 g / g, and a gel solid content of 48.2 mass%. After drying at a drying temperature of 190 ° C., the particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water absorbent resin (e5) had a CRC of 31.0 g / g (CRC increase from the hydrogel before drying = +3.5 g / g) and a solid content of 97.6 mass%.

[0212] [Comparative Example 6] No hydrogen peroxide The same operation as in Example 5 was performed except that no aqueous hydrogen peroxide solution was used in the polymerization step, and the amount of deionized water used in preparing the monomer composition was 407.2 g. A particulate hydrogel (d6) was obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%. The obtained particulate hydrogel (d6) had a gel particle size of 600 μm, a CRC of 36.8 g / g, and a gel solid content of 46.9 mass%. The particle size and distribution of the water-absorbent resin (e6) were adjusted in the same manner as in Example 1, and the CRC was 41.5 g / g (CRC increase from the hydrogel before drying = +4.7 g / g), and the solid content was 96.7 mass%.

[0213] [Comparative Example 7] Persulfate was added instead of hydrogen peroxide during the gel crushing process The same operation as in Example 8 was performed except that the 0.08% by mass hydrogen peroxide aqueous solution was changed to a 0.4% by mass sodium persulfate (NaPS) aqueous solution, and a particulate hydrogel (d7) and a water-absorbent resin (e7) were obtained. The obtained particulate hydrogel (d7) had a gel particle size of 620 μm, a CRC of 34.1 g / g, a gel solid content of 47.0% by mass, and a sodium persulfate content of 1000 ppm. After drying the particulate hydrogel (d7), the particle size and its distribution were adjusted in the same manner as in Example 1, and the obtained water-absorbent resin (e7) had a CRC of 48.0 g / g (CRC increase from the hydrogel before drying = +13.9 g / g) and a solid content of 96.3% by mass.

[0214] [Comparative Example 8] No hydrogen peroxide The same operation as in Example 1 was performed except that the amount of deionized water used in preparing the monomer composition was changed to 406.7 g, the amount of polyethylene glycol diacrylate (PEGDA) aqueous solution was changed to 0.92 g (PEGDA 0.003 mol% relative to the monomer), and no hydrogen peroxide aqueous solution was used. A hydrogel (d8) was obtained by polymerization of a monomer composition with a monomer concentration of 43 mass% / acrylic acid neutralization rate of 73 mol%. The hydrogel (d8) was prepared under the same conditions as the gel crushing in Example 1, but unlike Example 1, the load on the meat chopper crushing was high and a particulate hydrogel could not be obtained.

[0215] (a) Water absorption capacity without pressure (CRC) (NWSP 241.0.R2(15)) The water absorption capacity without load (CRC) was measured according to NWSP 241.0.R2(15). That is, 0.200g (mass W0(g)) of the water-absorbent resin was weighed, uniformly placed in a nonwoven bag (60×85mm) and heat-sealed, and then immersed in 500mL of 0.90% by mass sodium chloride aqueous solution adjusted to 23±2°C. After 30 minutes, the bag was pulled up and drained at 250G for 3 minutes using a centrifuge (Kokusan Co., Ltd. Centrifuge: Model H-122). Thereafter, the mass (W1(g)) of the bag was measured. The same operation was performed without adding the water-absorbent resin, and the mass (W2(g)) of the bag at that time was measured. The water absorption capacity without load (CRC) was calculated from the obtained W0(g), W1(g), and W2(g) according to the following (Formula 1).

[0216]

number

[0217] The CRC of the hydrogel (gel CRC) was determined by using a hydrogel-like cross-linked polymer of 0.4 (mass msi(g)) The same procedure as above was carried out, except that the free swelling time was 24 hours and the solid content of the hydrogel crosslinked polymer was measured separately according to (d) described below, and the gel CRC was calculated according to the following formula (2). Each sample was measured five times, and the average value was used.

[0218]

number

[0219] Here, msi: Mass of the hydrogel cross-linked polymer before measurement (g) mb: Mass (g) of blank (nonwoven fabric only) after free swelling and draining mwi: Mass (g) of the hydrogel crosslinked polymer after free swelling and draining Wn: solid content (mass%) of the hydrogel crosslinked polymer.

[0220] (b) Particle size distribution, mass average particle size (D50) and logarithmic standard deviation (σζ) of the water-absorbent resin Particulate water absorbent resin Mass average particle diameter (D50) The particle size distribution (σζ) of the water-absorbent resin measured by sieve classification and the logarithmic standard deviation of the particle size distribution (σζ) were measured in accordance with the measurement method disclosed in US Patent Application Publication No. 2006 / 204755.

[0221] (c) Solid content and moisture content Approximately 1 g of water-absorbent resin (water-absorbing agent) was weighed (mass W9 (g)) into an aluminum cup (mass W8 (g)) with a bottom diameter of 50 mm, and left to stand for 3 hours in a windless dryer at 180°C to dry. The total mass (W10 (g)) of the aluminum cup and water-absorbent resin (water-absorbing agent) after drying was measured, and the solid content was calculated using the following formula 4. The moisture content was calculated using the following formula 5.

[0222]

number

[0223]

number

[0224] (d) Solid content (gel solid content) and water content of hydrous gel The moisture content of the hydrous gel before drying was measured in the above (c) with 2.0 g of hydrous gel and 24 hours of drying time. After 2.00 g of the water-absorbent resin (hydrous gel) was placed in an aluminum cup with a bottom diameter of 50 mm, the total mass W1 (g) of the sample (water-absorbent resin and aluminum cup) was accurately weighed. Next, the sample was placed in an oven with an atmospheric temperature set to 180°C. After 24 hours, the sample was removed from the oven and the total mass W2 (g) was accurately weighed. When the mass of the water-absorbent resin (hydrous gel) used in this measurement was M (g), the moisture content (100-α) (mass%) of the water-absorbent resin (hydrous gel) was calculated according to the following (Equation 6). Here, α is the solid content (mass%) of the water-absorbent resin (hydrous gel). (100-α) (mass%) = {(W1-W2) / M} × 100 (Equation 6) (e) Particle size of particulate hydrogel Particle size of particulate hydrogel (mass average particle size (D50) Measurement was performed by the following method.

[0225] 20 g of particulate hydrogel (solid content α% by mass) at 20 to 25°C was added to 1000 g of 20% by mass aqueous sodium chloride solution (hereinafter referred to as "aqueous polyoxyethylene lauryl sulfate solution") containing 0.08% by mass sodium polyoxyethylene lauryl sulfate (surfactant) to prepare a dispersion, and the mixture was stirred at 300 rpm for 16 hours using a stirrer tip with a length of 50 mm and a diameter of 7 mm. The container used was a cylindrical polypropylene container (height 21 cm, diameter 8 cm, internal volume approximately 1.14 L).

[0226] After stirring, the above dispersion was poured into the center of a JIS standard sieve (diameter 21 cm, sieve openings: 8 mm / 4 mm / 2 mm / 1 mm / 0.60 mm / 0.30 mm / 0.15 mm / 0.075 mm) placed on a rotating plate. After washing out all the hydrous gel onto the sieve using 100 g of an aqueous solution of sodium polyoxyethylene lauryl sulfate, 6,000 g of an aqueous solution of sodium polyoxyethylene lauryl sulfate was poured from above using a shower (72 holes, liquid volume: 6.0 [L / min]) from a height of 30 cm to a water injection range (50 cm 2 ) was poured evenly over the sieve four times to classify the hydrous gel. The hydrous gel on the first sieve was drained for about 2 minutes and then weighed. The second and subsequent sieves were classified in the same manner, and the hydrous gel remaining on each sieve after draining was weighed. The sieves were changed appropriately depending on the gel particle size. For example, when the hydrous gel particle size was fine and clogging occurred with sieves with 0.15 mm or 0.075 mm openings, the sieves were replaced with larger diameter JIS standard sieves (diameter 30 cm, openings 0.15 mm, 0.075 mm) and classified.

[0227] The proportion (mass%) of the hydrous gel remaining on each sieve was calculated from the mass of the hydrous gel remaining on each sieve using the following formula (7). The mesh size of the sieve after draining was calculated using the following formula (8), and the particle size distribution of the hydrous gel was plotted on logarithmic probability paper. The particle size at which the cumulative sieve %R of the plot corresponds to 50 mass% was taken as the mass average particle size (D50) of the hydrous gel.

[0228] X(%)=(w / W)×100 (Formula 7) R(α)(mm)=(20 / W)1 / 3×r (Formula 8) In addition, in (Equation 7) and (Equation 8), X: Mass percentage (%) of the hydrous gel remaining on each sieve after classification and draining w: Mass (g) of the hydrogel remaining on each sieve after classification and draining W: Total mass of the hydrogel remaining on each sieve after classification and draining (g) R(α): Sieve opening (mm) when converted into a hydrous gel with solid content α (mass%) r: The mesh size (mm) of the sieve used to classify the hydrogel-like crosslinked polymer (hydrogel particles) swollen in a 20% by mass aqueous sodium chloride solution.

[0229] (f) Mass average particle size (d1) of the hydrogel converted into solid content under According to the above (Equation 9), the mass average particle diameter in terms of solid content (mass average particle diameter of the hydrogel particles after drying) d1 was calculated. SolidD50(d1) = GelD50 × (α / 100) 1 / 3 ... (Formula 9) In addition, in (Equation 9), GelD50: Mass average particle size of hydrous gel particles (μm) α: Solid content of hydrogel particles (mass%) SolidD50(d1) : Mass average particle size (μm) of hydrogel particles converted to dry matter It is.

[0230] (g) Amount of hydrogen peroxide relative to the solid content in the (particulate) hydrogel 2 g of the hydrous gel, 12 g of 0.9% by mass sodium chloride aqueous solution, and 8 g of methanol (if the gel swells and cannot be stirred, the salt concentration or the amount of the aqueous solution or methanol is appropriately adjusted) were placed in a glass sample bottle with a screw cap (volume 50 ml, diameter 35 mm, height approximately 80 mm), and stirred at 300 rpm at room temperature in the dark using a 25 mm stirrer coated with Teflon (registered trademark). After 4 hours, the solution was removed and passed through a filter paper (manufactured by ADVANTEC, No. 2). 10.0 g of the solution was placed in a glass sample bottle with a screw cap (volume 20 ml, diameter 25 mm, height approximately 50 mm).

[0231] Immediately after that, 0.30 g of 2N sulfuric acid aqueous solution and 0.1 g of 30% titanium (IV) sulfate solution (manufactured by Wako Pure Chemical Industries, Ltd.) were added and stirred at room temperature in the dark. After 1 minute, the solution was transferred to a plastic 1 cm cell and the absorbance (measurement wavelength: 410 nm) was measured using a spectrophotometer (Hitachi Ratio Beam Spectrophotometer U-5100 type) (the absorbance of a mixture of 3 g of 0.9 mass% sodium chloride aqueous solution, 0.30 g of 2N sulfuric acid aqueous solution, and 0.1 g of 30% titanium (IV) sulfate solution was set to 0). The amount of hydrogen peroxide (ppm) in the hydrogel was calculated from the absorbance thus obtained.

[0232] In addition, a calibration curve was created from the absorbance determined by preparing mixtures of 60% by mass of 0.9% by mass sodium chloride aqueous solution and 40% by mass of methanol containing 0.0001% by mass, 0.0005% by mass, 0.0010% by mass, 0.0025% by mass, and 0.0050% by mass of hydrogen peroxide, respectively, and carrying out the above-mentioned operation.

[0233] When the equation for the calibration curve is hydrogen peroxide amount (ppm) = a × (absorbance) (a is a constant), the amount of hydrogen peroxide (ppm) relative to the solid content in the hydrogel is expressed by the following equation.

[0234]

number

[0235] (h) Amount of sodium persulfate relative to the solid content in the (particulate) hydrogel 3 g of hydrous gel and 100 g of 5 wt % sodium chloride aqueous solution (if the gel swells and cannot be stirred, the salt concentration or the amount of the aqueous solution is adjusted appropriately) were placed in a 260 ml polypropylene container with a lid, and the mixture was stirred at 500 rpm at room temperature in the dark using a 25 mm stirrer coated with Teflon (registered trademark). After 2 hours, the solution was taken out and passed through a filter (GL Sciences, GL Chromatodisc, water system 25A, pore size 0.45 μm). 5.00 g of the solution was placed in a glass sample bottle with a screw cap (volume 50 ml, diameter 35 mm, height about 80 mm). Immediately after that, 0.50 g of 44 wt % potassium iodide aqueous solution was added, and the mixture was stirred at room temperature in the dark. After 1 hour, the solution was transferred to a 1 cm plastic cell and the absorbance (measurement wavelength: 350 nm) was measured using a spectrophotometer (Hitachi Ratio Beam Spectrophotometer U-1100) (the absorbance of 5 g of 5 wt% sodium chloride aqueous solution to which 0.50 g of 44 wt% potassium iodide aqueous solution was added was set to 0.) The amount of sodium persulfate (ppm) in the hydrogel was calculated from the absorbance thus obtained.

[0236] In addition, a calibration curve was prepared from the absorbance determined by preparing 5 wt % aqueous sodium chloride solutions containing 0.0005 wt %, 0.0010 wt %, 0.0015 wt %, and 0.0020 wt % sodium persulfate, respectively, and carrying out the above-mentioned procedure.

[0237] When the equation for the calibration curve is sodium persulfate amount (ppm) = a × (absorbance) (a is a constant), the amount of sodium persulfate (ppm) relative to the solid content in the hydrogel is expressed by the following equation.

[0238]

number

[0239] The physical properties and results of each of the Examples and Comparative Examples are shown in Table 1 and FIG.

[0240] [Table 1-1]

[0241] [Table 1-2]

[0242] When comparing the current value (A) of the meat chopper (gel crushing device) when crushing the gel under conditions of the same crosslinker type (PEGDA or TMPTA) and the same amount of use, Examples 1, 2, and 8 (PEGDA = 0.0039 mol%) and Comparative Examples 1, 2, 3, and 7 (PEGDA = 0.0039 mol%) have the same current value A, and Examples 5, 6, and 10 and Comparative Example 6 (TMPTA = 0.026 mol%) also have the same current value A, and the load when crushing the gel was almost the same. In the gel crushing device, since the voltage (V) is constant, the current value (A) of the crushing device is proportional to the power consumption (W), and it can be said that it essentially indicates the amount of energy consumed.

[0243] Therefore, even though the load on the device during gel crushing is the same and the production efficiency is the same, compared to Comparative Examples 1, 2 and 3, in Examples 1, 2 and 8 in which 100 ppm or more of hydrogen peroxide was added and the hydrous gel was dried at a temperature exceeding 160°C, water absorbent resins with high CRC were obtained, and it is understood that the method of the present invention can obtain water absorbent resins with excellent absorption performance (CRC), such as Example 1 (CRC = 56.3 g / g), Example 2 (CRC = 60.1 g / g) and Example 8 (CRC = 61 g / g), compared to Comparative Example 1 (CRC after drying = 35 g / g).

[0244] In addition, when comparing Comparative Example 7 (PEGDA=0.039 mol% and no hydrogen peroxide) and Example 3 (PEGDA=0.075 mol% and 680 ppm hydrogen peroxide in the hydrogel before drying) in which a water-absorbent resin with the same CRC (about 48 to 49 g / g) was obtained, the current value A when the gel was crushed using a meat chopper was lower in Example 3 than in Comparative Example 7 (no hydrogen peroxide) as a method for producing a water-absorbent resin that obtains the same water absorption capacity (CRC). From these comparisons, it was shown that it is possible to reduce the load on the production device and the energy consumption even when producing a water-absorbent resin that shows the same water absorption performance. In addition, for Examples 4, 9, and 11, the current value A (actual power consumption W because the voltage is constant) when the gel was crushed using a meat chopper was lower than in Comparative Examples 1 and 7 (no hydrogen peroxide) as a method for producing a water-absorbent resin that obtains the same water absorption capacity (CRC).

[0245] In drying of hydrogels containing the same amount of hydrogen peroxide, a comparison between Comparative Example 2 (CRC=36 g / g when dried at 150°C) and Example 1 (CRC=56.3 / g when dried at 190°C) (70 ppm hydrogen peroxide in hydrogel) and a comparison between Comparative Example 3 (CRC=35.5 g / g when dried at 150°C) and Example 8 (CRC=61 g / g when dried at 190°C) (approximately 160 ppm hydrogen peroxide in hydrogel) show that a hydrogel containing 100 ppm or more of hydrogen peroxide and heated to a temperature exceeding 160°C exhibits a high water absorption capacity (CRC after drying before surface crosslinking is 40 g / g or more, or even 50 g / g or more). In the present invention, even if a water-absorbent resin having a high water-absorbency has been difficult to stably and continuously produced due to the stickiness of a hydrous gel-like crosslinked polymer, a water-absorbent resin having a high water-absorbency (CRC after drying and before surface crosslinking of 40 g / g or more, and even 50 g / g or more) can be stably produced by a method not disclosed in Patent Documents 1 to 4.

[0246] Comparing Examples 1 and 2 (PEGDA) and Examples 3 and 4 (TMPTA), in which the type of internal crosslinking agent was changed, it can be seen that this case can be widely applied regardless of the crosslinking agent, but it can also be seen that PEGDA, which has a polyethylene glycol structure, is easier to achieve a high water absorption capacity than TMPTA.

[0247] It is also clear from FIG. 1 that a water-absorbent resin with a higher water absorption capacity (g / g) can be obtained even with the same amount of crosslinker (mol %).

[0248] From Table 1, it can be seen that in the second production method of the present invention (high temperature initiation short-time polymerization (polymerization initiation at 78°C, polymerization time of 1 minute, and 100 to 2000 ppm hydrogen peroxide in Examples 1 to 7) / and the third production method of the present invention (hydrogen peroxide addition in the gel crushing step after polymerization (100 to 2000 ppm hydrogen peroxide in Examples 8 to 11)), 70 to 92 mass % of the added 100 to 2000 ppm hydrogen peroxide is contained in the hydrogel polymer provided to the drying step, and that the second and third production methods of the present invention can provide a hydrogel crosslinked polymer containing 50 ppm or more of hydrogen peroxide, which is necessary for the first production method of the present invention.

[0249] From Table 1 (Examples 1 to 14, Comparative Examples 1 to 8) and FIG. 1, it can be seen that the inclusion of 50 ppm or more of hydrogen peroxide in the hydrous gel and heating to a temperature exceeding 160° C. improves the handleability of the hydrous gel and provides a water-absorbent resin with a high water absorption capacity.

[0250] The advantages of the first to third production methods of the present invention are clear. Hydrogen peroxide is known as an example of a polymerization initiator for water-absorbent resins, but the above Patent Documents 1 to 14 do not suggest the production method of the present application and its effects using 50 ppm or more of hydrogen peroxide in a hydrogel before drying and heating at over 160°C.

[0251] This application is based on Japanese Patent Application No. 2021-013220, filed on January 29, 2021, the disclosure of which is incorporated by reference in its entirety into this specification.

Claims

1. a polymerization step of polymerizing a monomer composition containing an internal crosslinking agent and a monomer to obtain a hydrous gel-like crosslinked polymer; A drying step of drying the hydrogel crosslinked polymer to obtain a dried polymer, The hydrogel crosslinked polymer subjected to the drying step contains hydrogen peroxide in an amount of 50 ppm or more relative to the solid content mass of the hydrogel crosslinked polymer; and A method for producing a water-absorbent resin, wherein the hydrogel-like crosslinked polymer is heated during the drying step so that the maximum temperature reached exceeds 160°C, and / or the dried polymer is heated after the drying step so that the maximum temperature reached exceeds 160°C.

2. The manufacturing method described in claim 1, wherein in the polymerization process, the temperature of the monomer composition at the start of polymerization is 35°C or higher.

3. A gel crushing step of crushing the hydrogel crosslinked polymer obtained in the polymerization step, 3. The method according to claim 1, wherein the hydrogel crosslinked polymer subjected to the drying step is a particulate hydrogel crosslinked polymer crushed in the gel crushing step.

4. The method according to claim 3 , wherein in the gel-crushing step, hydrogen peroxide is added in an amount of 50 ppm or more relative to the solid content mass of the hydrogel-like crosslinked polymer.

5. A manufacturing method as described in claim 3 or 4, wherein the period from the gel crushing step to the drying step is within one hour.

6. The method according to any one of claims 1 to 5, wherein in the polymerization step, a monomer composition containing hydrogen peroxide in an amount of 50 ppm or more relative to the solid content is polymerized to obtain a hydrogel-like crosslinked polymer.

7. The production method according to any one of claims 1 to 6, wherein, in the polymerization step, a monomer concentration of the monomer composition is 30 mass% or more, a temperature of the monomer composition at the start of polymerization is 30°C or more, and a polymerization time from the start of polymerization to the time when the polymerization temperature reaches a maximum temperature is 30 minutes or less.

8. A manufacturing method described in claim 6 or 7, wherein the period from the polymerization step to the drying step is within one hour.

9. The method according to any one of claims 3 to 8, wherein the particulate hydrogel crosslinked polymer has a mass average particle size calculated on a solid content basis of 1000 µm or less.

10. In the polymerization step, the monomer contains an acid group-containing unsaturated monomer as a main component, The method according to any one of claims 1 to 9, wherein the molar ratio of the neutralized salt to the total molar ratio of the acid group-containing unsaturated monomer and its neutralized salt is 50 mol % or more.

11. The method according to any one of claims 1 to 10, wherein in the polymerization step, the amount of the internal crosslinking agent used is 0.005 mol % or more based on the total amount of the monomers.

12. The production method according to any one of claims 1 to 11, wherein in the polymerization step, the monomer composition has a monomer concentration of 30 to 70 mass%, the temperature of the monomer composition at the start of polymerization is 40°C or higher, and the polymerization time from the start of polymerization until the polymerization temperature reaches a maximum temperature is 5 minutes or less.

13. The method according to any one of claims 1 to 12, wherein the hydrogel crosslinked polymer is dried in a dryer heated to a temperature exceeding 160°C.

14. The method according to any one of claims 1 to 13, wherein the water absorbent resin after the drying step has a water absorption capacity (CRC) of 40 g / g or more.

15. The method for producing the water absorbent resin according to any one of claims 1 to 14, wherein the water absorbency before surface cross-linking (CRC) is 40 g / g or more.

16. The method according to any one of claims 1 to 15, wherein the hydrogel-like crosslinked polymer during the drying step and / or the dried polymer after the drying step is further surface crosslinked.

17. The method according to any one of claims 1 to 16, wherein the internal crosslinking agent has a polyethylene glycol structure.

18. A method for producing a hydrous gel-like cross-linked polymer according to any one of claims 1 to 17, wherein the hydrous gel-like cross-linked polymer has a water absorption capacity (CRC) of 50 g / g or less.

Citation Information

Patent Citations

  • Manufacturing method of high whiteness water absorption resin

    CN101045789A

  • Novel polymerization process

    JP1982034101A

  • Production of highly water-absorptive polymer

    JP1985001205A

  • Novel continuous polymerization

    JP1985055002A

  • Method and apparatus for continuously producing polymer and copolymer from water-soluble monomer

    JP1987156102A